Leakage through waste covers with small geomembrane wrinkles - Felix Y.H. Fan; R. Kerry Rowe; Richard W.I. Brachman; J. Van Gulck (Geotextiles and Geomembranes, 2026)

A severe winter storm record for southwestern Australia, 1830–2024 - Joëlle Gergis; Jarrad Rowe; Linden Ashcroft; Zak Baillie; Blair Trewin; Rob J. Allan; Tessa Ellwood; Stefan Ingallina (Climate Dynamics, 2026)
This study describes the development of the longest sub-daily pressure record available from Australia and the Southern Hemisphere. We present newly consolidated mean sea level pressure observations for Perth in southwestern Australia, spanning 1830–2024. After establishing the quality of the new sub-daily pressure record, we evaluate its ability to resolve severe storms, verifying them against the synoptic fields generated by the 20th Century Reanalysis and independent historical records. We calculate a severe storm index for Perth using extreme pressure changes to assess any long-term changes in austral winter (June–August) storm activity back to 1830. Our results show a 20.2% decrease in the number of winter storms influencing Perth since 1970, with the decline further strengthening to 30.9% since 1990. The most recent decade (2010–2019) shows the lowest number of storms compared with any other decade since 1830. A supporting analysis of Perth rain days since 1830 displays considerable inter-annual variability and a notable reduction in winter rainfall since the 1970s. These results provide further evidence of a drying trend across southern Australia previously attributed to anthropogenically-influenced shifts in westerly storm tracks and changes in storm characteristics. We also identify a protracted dry period between 1830–1846 that is more pronounced than the current rainfall deficit. This analysis suggests that twentieth and twenty-first century weather observations do not capture the range of natural variability and extremes recorded in pre-industrial records, implying that future weather and climate risk is likely to be underestimated in the Australian region.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Faunal community ecology of central-eastern Indian Ocean Seamounts - Timothy D. O'Hara; Shane T. Ahyong; Phil Alderslade; Dianne Bray; Francesco Criscione; Niki Davey; Caroline Farrelly; Martin F. Gomon; Ana Hara; Jeremy Horowitz; Andrew M. Hosie; Lisa Kirkendale; et al. (Deep Sea Research Part II: Topical Studies in Oceanography, 2026)

Impact of diagenesis and acidic alteration on microbial fabrics and trace element distributions in fossilised siliceous hot spring deposits - Barbara J. Lyon; Michael C. Rowe; Andrew Langendam; Kathleen A. Campbell; Diego M. Guido; Ayrton R. Hamilton; Ema E. Nersezova; Amanda Galar; Dominique A. Stallard (Geochimica et Cosmochimica Acta, 2026)

Estimating mercury exposure in amphibians using non-lethal tissue sampling - Caitlin T. Rumrill; Kelly L. Smalling; Colleen Emery; Blake R. Hossack; Brian J. Halstead; Michael J. Adams; Adam R. Backlin; Adrianne B. Brand; Jon M. Davenport; Robert N. Fisher; Jill Fleming; Brad M. Glorioso; et al. (Ecotoxicology, 2026)

Pink Cricket Club: Dramatic color change in a Neotropical leaf‐masquerading katydid ( Arota festae , Griffini, 1896) - J. Benito Wainwright; Zeke W. Rowe; Matthew P. Greenwell; Patrick G. Cannon; Nathan W. Bailey; Graeme D. Ruxton (Ecology, 2026)

Assessing methane production and feed efficiency in both growing and mature ovine animals in six countries across Europe, South America and Oceania - Fiona.M. McGovern; Patricia L. Johnson; Noirin McHugh; Flavie Tortereau; Christel Marie-Etancelin; Elly A. Navajas; Ignacio De Barbieri; Bente Aspeholen Åby; Suzanne J. Rowe; Joanne Conington; Gabriel Ciappesoni; Ingjerd Dønnem; et al. (Small Ruminant Research, 2026)

Adopted “mammoths” from Alaska turn out to be a whale's tale - Matthew J. Wooller; Pat Drukenmiller; Gonzalo Oteo‐García; Francesca Di Paolo; Love Dalén; Nick Baker; Nancy Bigelow; Stormy Fields; Sambit Ghosh; Kathryn E. Krasinski; Ben Lamm; Alistair J. Monteath; et al. (Journal of Quaternary Science, 2026)
Radiocarbon‐dated fossils indicate woolly mammoths were extirpated from mainland Beringia around 13 000 years ago. However, environmental DNA in permafrost suggests small “cryptic“ populations survived into the Holocene. Resolving this discrepancy is crucial to understanding the drivers of mammoth extinction. The Adopt‐a‐Mammoth project, launched in 2022, is increasing the number of radiocarbon‐dated mammoth fossils to locate the chronologically youngest specimens. Here, we report results from two “mammoth“ vertebral epiphyseal plates from interior Alaska that produced the youngest radiocarbon ages associated with mammoth specimens (~1900–2700 cal a BP). However, isotopic data indicated that these individuals consumed marine resources, and subsequent ancient DNA analysis revealed the specimens were in fact from a North Pacific Right whale and a Minke whale. Solving the mystery of recent “mammoth” fossils raised new questions. How did the remains of ancient whales become emplaced in sediment so far from the coastline? We briefly consider four scenarios to account for this.

Genomics Reveals Extensive Population Structure and Undescribed Phylogenetic Relationships in the Cascade Torrent Salamander ( Rhyacotriton cascadae ) - Christopher D. Cousins; Deanna H. Olson; Lindsay S. Millward; Michael J. Adams; Christopher A. Pearl; Jennifer C. Rowe; Tiffany S. Garcia (Journal of Biogeography, 2026)
Aim Aims of the study are to examine patterns of range‐wide genetic differentiation and population structure in a headwater obligate salamander living in a geologically rich region, to identify genetically distinct populations and areas of gene flow between them. Location Oregon and Washington in the Pacific Northwest, United States of America. Time Period Tissue samples were collected in 2022 and 2023. Major Taxa Studied The Cascade torrent salamander Rhyacotriton cascadae . Methods Utilisation of a genome‐wide single nucleotide polymorphism (SNP) dataset from across the species range to conduct a principal components analysis (PCA), Bayesian model of population structure, co‐ancestry matrix, phylogenetic tree and estimate genetic diversity. Results There are extensive levels of population structure within R. cascadae , including a previously unknown and highly differentiated clade. Structure is characterised by an island‐like pattern wherein the species is comprised of six populations that function as independent demographic units, with gene flow largely constrained within populations. Main Conclusions Our findings reveal cryptic population structure within R. cascadae , identifying six distinct populations across the range. The northernmost population in the northwest of the species range in Washington is surprisingly highly divergent from the other five populations, and the divergence was not previously known to science. While major rivers act as phylogeographic boundaries between some populations, these boundaries appear to not always be complete.

An initial map of European intertidal seagrass - Bede Ffinian Rowe Davies; Simon Oiry; Mar Roca; Philippe Rosa; Maria Laura Zoffoli; Dimitris Poursanidis; Tobias Dolch; Bárbara Ondiviela; Cristina Galván; Ana C. Brito; Richard J. Lilley; Laura L. Govers; et al. (Remote Sensing of Environment, 2026)

Climate change–induced terrestrial matter runoff may decrease food web production in coastal ecosystems - Owen F. Rowe; Joanna Paczkowska; Andreas Brutemark; Sonia Brugel; Sachia J. Traving; Robert Lefébure; Fernanda Miranda; Liudmyla Guleikova; Evelina Griniene; Iveta Jurgensone; Pär Byström; Lasse Riemann; et al. (Limnology and Oceanography, 2025)
Climate change is projected to cause elevated precipitation in northern Europe, leading to increased runoff of terrestrial matter to coastal areas. The consequences for food web production and ecosystem function remain unclear. A mesocosm experiment was performed to investigate the impacts of elevated terrestrial matter input, using a natural plankton community from the northern Baltic Sea with added young‐of‐the‐year perch as planktivorous top consumer. Addition of terrestrial matter caused water browning and increased dissolved organic carbon and inorganic nutrient concentrations. Phytoplankton primary production showed a negative response to terrestrial matter due to decreased light availability, while heterotrophic bacterial production increased. The trophic balance, calculated as the difference between primary production and heterotrophic bacterial production, indicated that net‐heterotrophy was triggered by terrestrial matter enrichment. Primary production was identified as the main basal energy source for fish. Addition of terrestrial matter reduced the food web efficiency, calculated as the ratio between fish production and basal production (primary production + heterotrophic bacterial production). Furthermore, stable isotope analysis of seston and fish indicated that the added terrestrial matter was not efficiently incorporated in the food web and only marginally altered the food web trophic positions. The results suggest that the main food chain consisted of phytoplankton, mesozooplankton, and fish, and that the ecosystem production was overall light driven. Under a changing climate, several negative effects can be expected, including a poorer light climate, reduced ecosystem production and net‐heterotrophy. These alterations have potentially significant consequences for ecosystem functioning, fish production, and thus ecosystem services.

Decrypting the messages in the matrix: The proceedings of a symposium on dairy food matrix science and public health opportunities - Kevin B. Comerford; Allison L. Unger; Christopher J. Cifelli; Emma Feeney; Sylvia Rowe; Connie Weaver; Katie Brown (Critical Reviews in Food Science and Nutrition, 2025)

Life and death of a sinter archive: Evolution of siliceous hot-spring deposits (Holocene) on the dynamic Paeroa Fault at Te Kopia, Taupō Volcanic Zone, New Zealand - M.C. Rowe; K.A. Campbell; A. Hamilton; Y. Jiang; J. Pelser; B. Murphy; R. Martin; K.M. Mackenzie; D.A. Stallard; B. Lyon; A. Langendam; E.E. Nersezova; et al. (Journal of Volcanology and Geothermal Research, 2025)

Forest Topsoil Organic Carbon Declines Under Ash Dieback - Fiona M. Seaton; David A. Robinson; Claire M. Wood; Clare M. H. Benskin; Rebecca L. Rowe; Karen Hornigold; Keith J. Kirby; Chris Nichols; Simon M. Smart (Global Change Biology, 2025)
Tree diseases are increasingly affecting woodland ecosystems across the world. However, the impact of these diseases upon the soil, and in particular soil carbon, is still poorly understood. Here we present the results of a field survey of ~100 woodlands across Great Britain measured in 1971, 2001 and 2022 and evaluate the fifty‐year trend in topsoil (0–15 cm) carbon based upon measurements of soil organic matter (SOM) and the impact of Hymenoscyphus fraxineus (ash dieback). To better represent the full SOM distribution, including the extremely high SOM measurements, we adopt a Beta mixture modelling approach within a Bayesian framework. Across all woodlands, comprising ~1,500 plots per survey, average SOM remained constant across the fifty‐year time series. However, the 311 plots with ash dieback had lower SOM in the most recent survey compared to the 328 plots with ash trees present but no dieback recorded, due to a slight decline in SOM under ash dieback. This resulted in plots with ash dieback having a modelled mean SOM of 12.2% compared to 13.4% in plots without ash dieback, a difference of 1.23 percentage points (95% CI 0.25–2.21). Ash dieback was more likely to be recorded in plots that had higher soil pH pre‐ash dieback invasion, but the decline in SOM under ash dieback was not explained by changes in soil pH or changes in the ground flora composition. Converting our results to soil C and extrapolating for broadleaved woodland across the entirety of Great Britain, the total amount of topsoil carbon lost to date due to ash dieback could be 6 MtCO 2 (± 4 s.d.). Our results show the importance of understanding the impacts of tree disease when considering current and future woodland carbon dynamics.

Comparison of country-specific predictions of feed intake and methane emissions in sheep using different proxies - Q. Le Graverand; N. Lambe; F. McGovern; E.A. Navajas; P. Johnson; N. McHugh; I. De Barbieri; G. Ciappesoni; S. Rowe; B.A. Åby; J. Conington; C. Marie-Etancelin; et al. (Livestock Science, 2025)

Evaluation of Rock Burstability with Mechanical Property Testing and Microscopic Image Analysis - J. Malki; I. Vennes; C. D. Rowe; H. S. Mitri (Rock Mechanics and Rock Engineering, 2025)

Trophic ecology of groundfishes in nearshore areas of the Gulf of Maine - Landon P. Falke; Brian E. Smith; Stacy Rowe; Rebecca J. Peters; Timothy F. Sheehan (Journal of Fish Biology, 2025)
Ecosystem management requires an integrated understanding of ecological interactions. In the Gulf of Maine (GoM), trophic information pertaining to commercially important groundfishes and nearshore prey communities is lacking. We characterized nearshore communities and groundfish diets using data collected from nearshore surveys (864 bottom trawls and 3638 stomach samples of six groundfish species) conducted biannually (spring and fall) in Midcoast Maine and Penobscot Bay from 2012 to 2022. Groundfish diets were dominated by some of the most available nearshore prey (gadiform and clupeiform fishes and pandalid and crangonid shrimps). Shifts in relative prey availability over environmental gradients (e.g., depth and position along the coast), across seasons, and over years corresponded with parallel patterns in prey contributions to groundfish diets in specific predator–prey interactions. Negative trends in the relative availability and diet occurrence of signature GoM prey taxa (Northern shrimp Pandalus borealis , Atlantic herring Clupea harengus , and euphausiids) indicate that broader ecosystem changes, such as steady rises in water temperature and shifts in species distributions, are impacting nearshore trophic dynamics in the GoM. These observations provide timely information on mechanisms that underlie groundfish productivity and warrant inclusion of nearshore trophic dynamics in relevant ecosystem models.

A new approach for assessing the radioecological risk associated with the legacy discharge of oil derived natural radioactivity in the UK North Sea - F. Dal Molin; D. Hunt; A. Dewar; S. Lozach; C. Phillips; B. Thomas; L. Warford; J.E. Parker; J. Walker; M. Chocholek; D.M. Paterson; H. Woodward-Rowe; et al. (Marine Pollution Bulletin, 2025)

Mudstone diagenesis in the Cenomanian–Turonian Eagle Ford Group in the San Marcos Arch area. PART I: Chemostratigraphy, early diagenesis, bitumen expulsion and migration pathways - Lucy T. Ko; Robert G. Loucks; Harry Rowe; Robert M. Reed; J. Evan Sivil; Rieko Adriaens (Marine and Petroleum Geology, 2025)

Comparison of Laboratory Confirmed Drugs in Acute Recreational Drug Toxicity Presentations to an Urban Hospital in London, UK, 2016/17 versus 2019/20 - Caitlin E Wolfe; Lachlan J Sund; John RH Archer; Ashley Rowe; Simon Hudson; David M Wood; Paul I Dargan (Journal of Medical Toxicology, 2025)
Introduction Novel Psychoactive Substance (NPS) use is increasingly prevalent and is often associated with severe acute recreational drug toxicity (ARDT). 258 UK deaths were attributed to NPS use in 2021. Confirmatory testing which identifies NPS is limited by expense and timeliness. We aimed to identify NPS and other recreational drugs in a sample of 1000 ARDT presentations to a central London hospital in 2019/20 and to compare these drugs to those identified from a previous cohort in 2016/2017. Methods We prospectively enrolled 1000 serum samples from ARDT presentations to St Thomas’ Hospital between February 2019 and February 2020. Serum samples were deidentified and underwent qualitative analysis via mass spectrometry. Results were returned at the conclusion of testing and statistical analysis performed using ‘R’ (R Foundation for Statistical Computing). Results Twenty-eight unique NPS were detected in 2019/20, compared to 31 in 2016/17. Eight new NPS were detected in 2019/20: four benzodiazepines, two synthetic cannabinoid receptor agonists, one cathinone and one ketamine-analogue. No NPS opioids were detected in either cohort. Cannabis (16%,11% p = 0.02), ketamine (12%,7% p < 0.01) and opioids (57%,24% p < 0.01) were detected significantly more frequently in 2019/20 than in 2016/17, while alcohol (22%,49% p < 0.01), cathinones (1%,15% p < 0.01), GHB (14%,20% p < 0.01) and MDMA (9%,18% p < 0.01) were detected less frequently. Conclusions Studies that utilise confirmatory testing to detect NPS in presentations of ARDT provide important information for public health interventions. More NPS benzodiazepines and fewer NPS cathinones were detected in 2019/20, following temporal trends of forensic detection throughout Europe and reinforcing the importance of identifying emerging drugs.

Corrigendum to ‘Mudstone diagenesis with depth and thermal maturity in the Cenomanian–Turonian Eagle Ford Group. PART II: Diagenetic processes and paragenetic sequence’ [Mar. Petrol. Geol. 170 (2024) 107085 1–39] - Lucy T. Ko; Robert G. Loucks; Harry Rowe; Rieko Adriaens; J. Evan Sivil; Gilles Mertens (Marine and Petroleum Geology, 2024)

Mudstone diagenesis with depth and thermal maturity in the Cenomanian–Turonian Eagle Ford group. PART II: Diagenetic processes and paragenetic sequence - Lucy T. Ko; Robert G. Loucks; Harry Rowe; Rieko Adriaens; J. Evan Sivil; Gilles Mertens (Marine and Petroleum Geology, 2024)

Taxonomic and environmental significance of Poaceae and Cyperaceae phytoliths from the Northern Territory, Australia - Kelsey C. Boyd; Carlos E. Cordova; Haidee R. Cadd; Cassandra Rowe; Tim J. Cohen (Review of Palaeobotany and Palynology, 2024)

Woody plant phytolith morphology and representation in surface sediments across the Northern Territory, Australia - Kelsey C. Boyd; Carlos E. Cordova; Haidee R. Cadd; Cassandra Rowe; Tim J. Cohen (Review of Palaeobotany and Palynology, 2024)

Intertidal seagrass extent from Sentinel-2 time-series show distinct trajectories in Western Europe - Bede Ffinian Rowe Davies; Simon Oiry; Philippe Rosa; Maria Laura Zoffoli; Ana I. Sousa; Oliver R. Thomas; Dan A. Smale; Melanie C. Austen; Lauren Biermann; Martin J. Attrill; Alejandro Roman; Gabriel Navarro; et al. (Remote Sensing of Environment, 2024)

Can the cross-education of strength attenuate the impact of detraining after a period of strength training? A quasi-randomized trial - Grant S. Rowe; Anthony J. Blazevich; Janet L. Taylor; Timothy Pulverenti; G. Gregory Haff (European Journal of Applied Physiology, 2024)
Purpose Unilateral strength training may attenuate the decline in muscle strength and size in homologous, contralateral muscles. This study aimed to determine whether the cross-education of strength could specifically attenuate the effects of detraining immediately after a short (prehabilitation-type) period of strength training. Methods Twenty-six strength-trained participants were assigned to either four weeks of unilateral strength training of the stronger arm (UNI) or detraining (Detrain). Motor evoked potential (MEP) and cortical silent period (cSP) responses, muscle cross-sectional area (CSA Flexor ; peripheral quantitative computed tomography) and maximal strength, rate of force development (RFD) and muscle activation (EMG) were examined in both elbow flexors before and after the intervention period. Results In UNI, one-repetition maximum (1-RM) strength improved in both the trained (∆ = 2.0 ± 0.9 kg) and non-trained (∆ = 0.8 ± 0.9 kg) arms despite cessation of training of the weaker arm, whereas 1-RM strength was unchanged in Detrain. Maximal voluntary isometric contraction, isokinetic peak torque, and RFD did not change in either group. No neural changes were detected in UNI, but cSP increased in Detrain (∆ = 0.010 ± 0.015 s). CSA Flexor increased in the trained arm (∆ = 51 ± 43 mm 2 ) but decreased in the non-trained arm (∆ = -53 ± 50 mm 2 ) in UNI. CSA Flexor decreased in both arms in Detrain and at a similar rate to the non-trained arm in UNI. Conclusion UNI attenuated the effects of detraining in the weaker arm as shown by the improvement in 1-RM strength. However, the cross-education of strength did not attenuate the decline in muscle size in the contralateral arm.

Modeling nearshore total phosphorus in Lake Michigan using linked hydrodynamic and water quality models - James J. Pauer; Mark D. Rowe; Wilson Melendez; Thomas P. Hollenhorst; Lisa L. Lowe; Peter J. Alsip; Dale M. Robertson; Steven A. Pothoven (Ecological Modelling, 2024)

Early Aboriginal pottery production and offshore island occupation on Jiigurru (Lizard Island group), Great Barrier Reef, Australia - Sean Ulm; Ian J. McNiven; Glenn R. Summerhayes; Pei-hua Wu; Magdalena M.E. Bunbury; Fiona Petchey; Quan Hua; Robert Skelly; Ariana B.J. Lambrides; Cassandra Rowe; Kelsey M. Lowe; Christian H. Reepmeyer; et al. (Quaternary Science Reviews, 2024)

Synergy between industry and agriculture: Techno-economic and life cycle assessments of waste recovery for crop growth in glasshouses - Lewis J. McDonald; Ariane S.S. Pinto; Muhammad Naveed Arshad; Rebecca L. Rowe; Iain Donnison; Marcelle McManus (Journal of Cleaner Production, 2023)

Adjacent and downstream effects of forest harvest on the distribution and abundance of larval headwater stream amphibians in the Oregon Coast Range - Adam Duarte; Nathan D. Chelgren; Jennifer C. Rowe; Christopher A. Pearl; Sherri L. Johnson; Michael J. Adams (Forest Ecology and Management, 2023)

The Management of Non-IgE-mediated Allergies in Human Milk Fed Infants - S. Rowe; H. Lima; A. Licata; J. Hoffman; R. Durban (Journal of the Academy of Nutrition and Dietetics, 2023)

Hypothalamus volumes in adolescent Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS): impact of self-reported fatigue and illness duration - Hollie Byrne; Elisha K. Josev; Sarah J. Knight; Adam Scheinberg; Katherine Rowe; Lionel Lubitz; Marc L. Seal (Brain Structure and Function, 2023)
Adolescent Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) is a complex illness of unknown aetiology. Emerging theories suggest ME/CFS may reflect a progressive, aberrant state of homeostasis caused by disturbances within the hypothalamus, yet few studies have investigated this using magnetic resonance imaging in adolescents with ME/CFS. We conducted a volumetric analysis to investigate whether whole and regional hypothalamus volumes in adolescents with ME/CFS differed compared to healthy controls, and whether these volumes were associated with fatigue severity and illness duration. 48 adolescents (25 ME/CFS, 23 controls) were recruited. Lateralised whole and regional hypothalamus volumes, including the anterior–superior, superior tubular, posterior, anterior-inferior and inferior tubular subregions, were calculated from T1-weighted images. When controlling for age, sex and intracranial volume, Bayesian linear regression models revealed no evidence for differences in hypothalamus volumes between groups. However, in the ME/CFS group, a weak linear relationship between increased right anterior–superior volumes and fatigue severity was identified, which was absent in controls. In addition, Bayesian quantile regression revealed a likely-positive association between illness duration and right superior tubular volumes in the ME/CFS group. While these findings suggest overall comparability in regional and whole hypothalamus volumes between adolescents with ME/CFS and controls, preliminary evidence was identified to suggest greater fatigue severity and longer illness duration were associated with greater right anterior–superior and superior-tubular volumes, respectively. These regions contain the anterior and superior divisions of the paraventricular nucleus, involved in the neuroendocrine response to stress, suggesting involvement in ME/CFS pathophysiology. However, replication in a larger, longitudinal cohort is required.

Geographic and taxonomic variation in adaptive capacity among mountain-dwelling small mammals: Implications for conservation status and actions - Erik A. Beever; Jennifer L. Wilkening; Peter D. Billman; Lindsey L. Thurman; Kristina A. Ernest; David H. Wright; Alisha M. Gill; April C. Craighead; Nolan A. Helmstetter; Leona K. Svancara; Meghan J. Camp; Sabuj Bhattacharyya; et al. (Biological Conservation, 2023)

Wind and small mammals are complementary fungal dispersers - Benjamin W. Borgmann‐Winter; Ryan B. Stephens; Mark A. Anthony; Serita D. Frey; Anthony W. D'Amato; Rebecca J. Rowe (Ecology, 2023)
Following a disturbance, dispersal shapes community composition as well as ecosystem structure and function. For fungi, dispersal is often wind or mammal facilitated, but it is unclear whether these pathways are complementary or redundant in the taxa they disperse and the ecosystem functions they provide. Here, we compare the diversity and morphology of fungi dispersed by wind and three rodent species in recently harvested forests using a combination of microscopy and Illumina sequencing. We demonstrate that fungal communities dispersed by wind and small mammals differ in richness and composition. Most wind‐dispersed fungi are wood saprotrophs, litter saprotrophs, and plant pathogens, whereas fungi dispersed in mammal scat are primarily mycorrhizal, soil saprotrophs, and unspecified saprotrophs. We note substantial dispersal of truffles and agaricoid mushrooms by small mammals, and dispersal of agaricoid mushrooms, crusts, and polypores by wind. In addition, we find mammal‐dispersed spores are larger than wind‐dispersed spores. Our findings suggest that wind‐ and small‐mammal‐facilitated dispersal are complementary processes and highlight the role of small mammals in dispersing mycorrhizal fungi, particularly following disturbances such as timber harvest.

The need to consider the service life of all components of a modern MSW landfill liner system - R. Kerry Rowe; J. Reinert; Y. Li; R. Awad (Waste Management, 2023)

Ecosystem benefits of adopting a whole‐site approach to MPA management - Bede Ffinian Rowe Davies; Luke Holmes; Martin J. Attrill; Emma V. Sheehan (Fisheries Management and Ecology, 2022)
Globally, nations are designating marine protected areas to recover and protect habitats and species. With targets to protect 30% of marine areas by 2030, the effectiveness of MPAs to protect designated space is important. In Lyme Bay (south‐west UK), two co‐located MPAs have each adopted different management styles to exclude mobile demersal fishing: a Special Area of Conservation (SAC) protecting the known extent of sensitive reef habitat and an area including a mosaic of reef and sedimentary habitats where the whole site is protected from mobile demersal fishing under a statutory instrument (SI). Underwater videography, both towed (individuals m −2 ) and baited (MaxN), was used to enumerate change over time of reef species (number of taxa, total abundance, functional richness and functional redundancy) in the MPAs and nearby control areas (2008–2019). Total abundance and functional redundancy of sessile taxa and functional richness of mobile taxa increased, while the number of sessile or mobile taxa, functional richness of sessile taxa, total abundance of mobile taxa or functional redundancy of mobile taxa did not differ from nearby control sites. Over time, both management styles did result in increases in sessile and sedentary taxa diversity relative to open controls, with increases in total abundance of 15% and 95% in the “feature‐based” and whole‐site MPAs, respectively, alongside increases in the number of sessile taxa of 44% over time in the “feature‐based” MPA. However, the mobile taxa in the whole‐site MPA showed levels of functional redundancy 7% higher than the “feature‐based” MPA, indicative of a higher community resilience inside the whole‐site MPA to perturbations, such as storms or biological invasions. Increases seen in the diversity of sessile taxa were expected only in areas where mobile demersal fishing was excluded (~46.8% of its areas). Therefore, if the whole “feature‐based” MPA was consistently protected, we expected to see similar levels of increase in the functional extent of reef. While the “feature‐based” MPA showed similar results over time to that of the “whole site,” the “whole site” showed higher levels of diversity, both taxonomical and functional.

A sulfur and halogen budget for the large magmatic system beneath Taupō volcano - Max S. Sharpe; Simon J. Barker; Shane M. Rooyakkers; Colin J. N. Wilson; Isabelle Chambefort; Michael C. Rowe; C. Ian Schipper; Bruce L. A. Charlier (Contributions to Mineralogy and Petrology, 2022)
The transport and degassing pathways of volatiles through large silicic magmatic systems are central to understanding geothermal fluid compositions, ore deposit genesis, and volcanic eruption dynamics and impacts. Here, we document sulfur (S), chlorine (Cl), and fluorine (F) concentrations in a range of host materials in eruptive deposits from Taupō volcano (New Zealand). Materials analysed are groundmass glass, silicic melt inclusions, and microphenocrystic apatite that equilibrated in shallow melt-dominant magma bodies; silicic melt and apatite inclusions within crystal cores inferred to be sourced from deeper crystal mush; and olivine-hosted basaltic melt inclusions from mafic enclaves that represent the most primitive feedstock magmas. Sulfur and halogen concentrations each follow distinct concentration pathways during magma differentiation in response to changing pressures, temperatures, oxygen fugacities, crystallising mineral phases, the effects of volatile saturation, and the presence of an aqueous fluid phase. Sulfur contents in the basaltic melt inclusions (~ 2000 ppm) are typical for arc-type magmas, but drop to near detection limits by dacitic compositions, reflecting pyrrhotite crystallisation at ~ 60 wt. % SiO 2 during the onset of magnetite crystallisation. In contrast, Cl increases from ~ 500 ppm in basalts to ~ 2500 ppm in dacitic compositions, due to incompatibility in the crystallising phases. Fluorine contents are similar between mafic and silicic compositions (< 1200 ppm) and are primarily controlled by the onset of apatite and/or amphibole crystallisation and then destabilisation. Sulfur and Cl partition strongly into an aqueous fluid and/or vapour phase in the shallow silicic system. Sulfur contents in the rhyolite melts are low, yet the Oruanui supereruption is associated with a major sulfate peak in ice core records in Antarctica and Greenland, implying that excess S was derived from a pre-eruptive gas phase, mafic magma recharge, and/or disintegration of a hydrothermal system. We estimate that the 25.5 ka Oruanui eruption ejected > 130 Tg of S (390 Tg sulfate) and up to ~ 1800 Tg of Cl, with potentially global impacts on climate and stratospheric ozone.

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Predicting larval alewife transport in Lake Michigan using hydrodynamic and Lagrangian particle dispersion models - Mark D. Rowe; Sara E. Prendergast; Karen M. Alofs; David B. Bunnell; Edward S. Rutherford; Eric J. Anderson (Limnology and Oceanography, 2022)
Several species of fish in large lakes and marine environments have a pelagic larval stage, and are subject to variable transport that can ultimately regulate survival and recruitment success. Alewife, Alosa pseudoharengus , are subject to transport by complex coastal currents during their pelagic larval stage (~ 30 d). We assessed backward‐trajectory simulations, consisting of a Lagrangian particle dispersion model linked to the Finite Volume Community Ocean Model, to estimate likely hatch locations of aged larval alewife collected from locations on both the eastern and western sides of Lake Michigan during July 2015. We used four deployments of three satellite‐tracked drifter buoys in coastal waters to assess model skill in estimating the origin of a drifter from its final location. We found that the trajectories of drifters varied greatly, depending on wind events and associated coastal transport processes, including upwelling/downwelling and coastal jet currents. In 2 of 12 cases, the backward trajectory simulations failed to predict the drifter origin, associated with transport of 170 km in a narrow coastal jet current. In the remaining 10 cases, the known drifter origin was within 3.5 km of the spatial patch of predicted possible origins for a scenario of horizontal diffusivity (188 m 2 s −1 ) consistent with the offshore model grid resolution. Modeled backward trajectories estimated that alewife originated from the same side of the lake where they were collected, within ~ 100 km of the collection site. Our paper demonstrates the utility of hydrodynamic models to estimate a region of origin for aged larval fish.

Small herbivores with big impacts: Tundra voles ( Microtus oeconomus ) alter post‐fire ecosystem dynamics - Jess K. Steketee; Adrian V. Rocha; Laura Gough; Kevin L. Griffin; Ian Klupar; Ruby An; Nicole Williamson; Rebecca J. Rowe (Ecology, 2022)
Fire is an important ecological disturbance that can reset ecosystems and initiate changes in plant community composition, ecosystem biogeochemistry, and primary productivity. As herbivores rely on primary producers for food, changes in vegetation may alter plant–herbivore interactions with important—but often unexplored—feedbacks to ecosystems. Here we examined the impact of post‐fire changes in plant community composition and structure on habitat suitability and rodent herbivore activity in response to a large, severe, and unprecedented fire in northern Alaskan tundra. In moist acidic tundra where the fire occurred, tundra voles ( Microtus oeconomus ) are the dominant herbivore and rely on the tussock forming sedge Eriophorum vaginatum for both food and nesting material. Tundra voles were 10 times more abundant at the burned site compared with nearby unburned tundra 7‐12 years after the fire. Fire increased the habitat suitability for voles by increasing plant productivity and biomass, food quality, and cover through both taller vegetation and increased microtopography. As a result of elevated vole abundance, Eriophorum mortality caused by vole herbivory was two orders of magnitude higher than natural mortality and approached the magnitude of the mortality rate resulting directly from the fire. These findings suggest that post‐fire increases in herbivore pressure on Eriophorum could, in turn, disrupt graminoid recovery and enhance shrub encroachment. Tundra state transitions from graminoid to shrub dominated are also evident following other disturbances and fertilization experiments, suggesting that as Arctic temperatures rise, greater available nutrients and increased frequencies of large‐scale disturbances may also alter plant–animal interactions with cascading impacts on plant communities and ecosystem function.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Long-lived dacitic magmatic systems and recharge dynamics in the Jemez Mountains volcanic field, western USA - Jie Wu; Michael C. Rowe; Shane J. Cronin; John A. Wolff; Bin Fu (Contributions to Mineralogy and Petrology, 2022)
We examine the connected history of dacite-dominant volcanic rocks of the Tschicoma Formation, erupted between 5.5 and 2 Ma from the Jemez Mountains volcanic field, western USA. Zircon samples from two separate eruptions have continuous SHRIMP U–Pb age spectra spanning 0.84–1.08 Myr duration (3.12–3.96 Ma and 3.50–4.58 Ma, respectively), following an episode of zircon crystallization 0.28–0.50 Myr earlier (at 4.46 Ma and 4.86 Ma, respectively). Zircon chemical variations, as well as ubiquitous resorption textures that commonly show large core-rim age differences (up to 720–740 kyr), suggest that they grew in separate melt lenses. Zircons were likely stored at near-solidus or even sub-solidus conditions after crystallization, but may have been reactivated in response to at least four major magma recharge events every 300–400 kyr and smaller events in between. A cycle of zircon dissolution (from heating), recrystallization (during cooling), and storage repeated in different locations in the Tschicoma mush system throughout its lifespan; each recharge-induced heating stage may last for several hundred to more than a thousand years based on calculations of zircon dissolution. We envisage the melt lenses to be distributed in a crystal mush zone, coalescing into a single magma batch as magma recharge occurs shortly before eruption. Once active, increasing magma supply rates may trigger large-scale partial melting of the pre-existing mush and caldera-forming eruptions.

Empirically derived thermal thresholds of four coral species along the Red Sea using a portable and standardized experimental approach - Nicolas R. Evensen; Christian R. Voolstra; Maoz Fine; Gabriela Perna; Carol Buitrago-López; Anny Cárdenas; Guilhem Banc-Prandi; Katherine Rowe; Daniel J. Barshis (Coral Reefs, 2022)
Global warming is causing an unprecedented loss of species and habitats worldwide. This is particularly apparent for tropical coral reefs, with an increasing number of reefs experiencing mass bleaching and mortality on an annual basis. As such, there is a growing need for a standardized experimental approach to rapidly assess the thermal limits of corals and predict the survival of coral species across reefs and regions. Using a portable experimental system, the Coral Bleaching Automated Stress System (CBASS), we conducted standardized 18 h acute thermal stress assays to quantitively determine the upper thermal limits of four coral species across the length of the Red Sea coastline, from the Gulf of Aqaba (GoA) to Djibouti (~ 2100 km). We measured dark-acclimated photosynthetic efficiency ( F v /F m ), algal symbiont density, chlorophyll a, and visual bleaching intensity following heat stress. F v /F m was the most precise response variable assessed, advancing the F v /F m effective dose 50 (ED50, i.e., the temperature at which 50% of the initial F v /F m is measured) as an empirically derived proxy for thermal tolerance. ED50 thermal thresholds from the central/southern Red Sea and Djibouti populations were consistently higher for Acropora hemprichii, Pocillopora verrucosa, and Stylophora pistillata (0.1–1.8 °C above GoA corals, respectively), in line with prevailing warmer maximum monthly means (MMMs), though were lower than GoA corals relative to site MMMs (1.5–3.0 °C). P. verrucosa had the lowest thresholds overall. Despite coming from the hottest site, thresholds were lowest for Porites lobata in the southern Red Sea, suggesting long-term physiological damage or ongoing recovery from a severe, prior bleaching event. Altogether, the CBASS resolved historical, taxonomic, and possibly recent environmental drivers of variation in coral thermal thresholds, highlighting the potential for a standardized, short-term thermal assay as a universal approach for assessing ecological and evolutionary variation in the upper thermal limits of corals.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Cell therapy rescues aging-induced beta-1 adrenergic receptor and GRK2 dysfunction in the coronary microcirculation - Gabrielle Rowe; Evan Tracy; Jason E. Beare; Amanda J. LeBlanc (GeroScience, 2022)

Contrasting heat stress response patterns of coral holobionts across the Red Sea suggest distinct mechanisms of thermal tolerance - Christian R. Voolstra; Jacob J. Valenzuela; Serdar Turkarslan; Anny Cárdenas; Benjamin C. C. Hume; Gabriela Perna; Carol Buitrago‐López; Katherine Rowe; Monica V. Orellana; Nitin S. Baliga; Suman Paranjape; Guilhem Banc‐Prandi; et al. (Molecular Ecology, 2021)
Corals from the northern Red Sea, in particular the Gulf of Aqaba (GoA), have exceptionally high bleaching thresholds approaching >5℃ above their maximum monthly mean (MMM) temperatures. These elevated thresholds are thought to be due to historical selection, as corals passed through the warmer Southern Red Sea during recolonization from the Arabian Sea. To test this hypothesis, we determined thermal tolerance thresholds of GoA versus central Red Sea (CRS) Stylophora pistillata corals using multi‐temperature acute thermal stress assays to determine thermal thresholds. Relative thermal thresholds of GoA and CRS corals were indeed similar and exceptionally high (~7℃ above MMM). However, absolute thermal thresholds of CRS corals were on average 3℃ above those of GoA corals. To explore the molecular underpinnings, we determined gene expression and microbiome response of the coral holobiont. Transcriptomic responses differed markedly, with a strong response to the thermal stress in GoA corals and their symbiotic algae versus a remarkably muted response in CRS colonies. Concomitant to this, coral and algal genes showed temperature‐induced expression in GoA corals, while exhibiting fixed high expression (front‐loading) in CRS corals. Bacterial community composition of GoA corals changed dramatically under heat stress, whereas CRS corals displayed stable assemblages. We interpret the response of GoA corals as that of a resilient population approaching a tipping point in contrast to a pattern of consistently elevated thermal resistance in CRS corals that cannot further attune. Such response differences suggest distinct thermal tolerance mechanisms that may affect the response of coral populations to ocean warming.

Mammals on mountainsides revisited: Trait‐based tests of assembly reveal the importance of abiotic filters - Brooks A. Kohli; Richard D. Stevens; Eric A. Rickart; Rebecca J. Rowe (Journal of Biogeography, 2021)
Aim Mountains provide uniquely informative systems for examining how biodiversity is distributed and identifying the causes of those patterns. Elevational patterns of species richness are well‐documented for many taxa but comparatively few studies have investigated patterns in multiple dimensions of biodiversity along mountainsides, which can reveal the underlying processes at play. Here, we use trait‐based diversity patterns to determine the role of abiotic filters and competition in the assembly of communities of small mammals across elevation and evaluate the surrogacy of taxonomic, functional, and phylogenetic dimensions of diversity. Location Great Basin ecoregion, western North America. Taxon Rodents and shrews. Methods The elevational distributions of 34 species were determined from comprehensive field surveys conducted in three arid, temperate mountain ranges. Elevation–diversity relationships and community assembly processes were inferred from phylogenetic (PD) and functional diversity (FD) patterns of mean pairwise and mean nearest‐neighbor distances while accounting for differences in species richness. FD indices were calculated separately for traits related to either abiotic filtering (β‐niche traits) or biotic interactions (α‐niche traits) to test explicit predictions of the role of each across elevation. Results Trait‐based tests of processes indicated that abiotic filtering tied to a strong aridity gradient drives the assembly of both low‐ and high‐elevation communities. Support for competition was not consistent with theoretical expectations under the stress‐dominance hypothesis, species interactions‐abiotic stress hypothesis, or guild assembly rule. Mid‐elevation peaks in species richness contrasted with overall FD and PD, which generally increased with elevation. PD and total FD were correlated on two of three mountains. Main conclusions The functional diversity of small mammal communities in these arid, temperate mountains is most consistent with abiotic filters, whereas support for competition is weak. Decomposing FD into traits related to separate assembly processes and examining ecoregional variation in diversity were critical for uncovering the generality of mechanisms. Divergent patterns among dimensions revealed species richness to be a poor surrogate for PD and FD across elevation and reflect the effect of biogeographic and evolutionary history. This first analysis of elevational multidimensional diversity gradients for temperate mammals provides a versatile framework for future comparative studies.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Life‐stage‐dependent supergene haplotype frequencies and metapopulation neutral genetic patterns of Atlantic cod, Gadus morhua , from Canada's Northern cod stock region and adjacent areas - Gregory Neils Puncher; Sherrylynn Rowe; George A. Rose; Geneviève J. Parent; Yanjun Wang; Scott A. Pavey (Journal of Fish Biology, 2021)
Among highly migratory fish species, nursery areas occupied by juveniles often differ from adult habitats. To better understand the spatial dynamics of Canada's Northern cod stock, juveniles caught off the east coast of Newfoundland and Labrador were compared to adults from the same region as well as individuals from other areas in Atlantic Canada using double‐digest restriction site‐associated DNA sequencing–derived single nucleotide polymorphisms. A reduced proportion of homozygotes with a chromosomal inversion located in linkage group 1 (LG1) was detected between juvenile and adult samples in the Northern cod stock region, potentially indicating age‐dependent habitat use or ontogenetic selection for attributes associated with the many genes located in LG1. No selectively neutral genetic differences were found between samples from the Northern cod stock; nevertheless, significant differences were found between some of these samples and cod collected from St. Pierre Bank, Bay of Fundy, Browns Bank and the southern Scotian Shelf. Clustering analysis of variants at neutral loci provided evidence for three major genetic units: (a) the Newfoundland Atlantic Coast, (b) eastern and southern Gulf of St. Lawrence and Burgeo Bank and (c) the Bay of Fundy, Browns Bank and southern Scotian Shelf. Both adaptive and neutral population structure within the Northern cod stock should be considered by managers to promote demographic rebuilding of the stock.

Monitoring wetland water quality related to livestock grazing in amphibian habitats - Kelly L. Smalling; Jennifer C. Rowe; Christopher A. Pearl; Luke R. Iwanowicz; Carrie E. Givens; Chauncey W. Anderson; Brome McCreary; Michael J. Adams (Environmental Monitoring and Assessment, 2021)
Land use alteration such as livestock grazing can affect water quality in habitats of at-risk wildlife species. Data from managed wetlands are needed to understand levels of exposure for aquatic life stages and monitor grazing-related changes afield. We quantified spatial and temporal variation in water quality in wetlands occupied by threatened Oregon spotted frog ( Rana pretiosa ) at Klamath Marsh National Wildlife Refuge in Oregon, United States (US). We used analyses for censored data to evaluate the importance of habitat type and grazing history in predicting concentrations of nutrients, turbidity, fecal indicator bacteria (FIB; total coliforms, Escherichia coli ( E. coli ), and enterococci), and estrogenicity, an indicator of estrogenic activity. Nutrients (orthophosphate and ammonia) and enterococci varied over time and space, while E. coli , total coliforms, turbidity, and estrogenicity were more strongly associated with local livestock grazing metrics. Turbidity was correlated with several grazing-related constituents and may be particularly useful for monitoring water quality in landscapes with livestock use. Concentrations of orthophosphate and estrogenicity were elevated at several sites relative to published health benchmarks, and their potential effects on Rana pretiosa warrant further investigation. Our data provided an initial assessment of potential exposure of amphibians to grazing-related constituents in western US wetlands. Increased monitoring of surface water quality and amphibian population status in combination with controlled laboratory toxicity studies could help inform future research and targeted management strategies for wetlands with both grazing and amphibians of conservation concern.

Resting-state functional connectivity, cognition, and fatigue in response to cognitive exertion: a novel study in adolescents with chronic fatigue syndrome - Elisha K. Josev; Charles B. Malpas; Marc L. Seal; Adam Scheinberg; Lionel Lubitz; Kathy Rowe; Sarah J. Knight (Brain Imaging and Behavior, 2020)

Modeling the interactive effects of nutrient loads, meteorology, and invasive mussels on suitable habitat for Bighead and Silver Carp in Lake Michigan - Peter J. Alsip; Hongyan Zhang; Mark D. Rowe; Edward Rutherford; Doran M. Mason; Catherine Riseng; Zhenming Su (Biological Invasions, 2020)
Anthropogenic stressors that affect ecological processes in the Laurentian Great Lakes can impact their susceptibility to bioinvasions. Bighead Hypophthalmichthys nobilis and Silver Carp H. molitrix , collectively ‘bigheaded carps’ (BHC), are planktivorous fishes threatening to invade Lake Michigan. While previous studies indicate the lake contains habitat suitable for BHC growth, there is a need to understand how anthropogenic-driven changes to the abiotic and biotic environment could alter its vulnerability to BHC. We applied a spatially explicit model of BHC growth rate potential (GRP; g g −1 d −1 ) to nine biophysical model scenarios to evaluate changes in habitat suitability in Lake Michigan. Scenarios differed in meteorology (cool, reference, warm), annual tributary phosphorus loads (0, 3300, and 5600 MTA), and the presence/absence of invasive dreissenid mussels. Mussel effects on BHC GRP relied on their contact with the surface mixed layer (SML), the depth of which was affected by meteorology. The warm year advanced the expansion of Bighead Carp habitat by increasing temperature-dependent foraging rates and lessening the time of competitive interaction with mussels due to earlier stratification separating mussels from the SML. Phosphorus loads were the most influential driver of the lake’s suitability. Compared to present conditions, we estimate BHC could have grown an additional 8–40% annually in the 1980s when mussels were not in the lake and phosphorus loads were higher. Our study demonstrates how climate change and nutrient enrichment can increase Lake Michigan’s vulnerability to BHC by affecting thermal regime and productivity, thereby limiting negative effects of dreissenid mussels on BHC growth.

The curious case of bunnies: interpretation of the lagomorph index from Homol’ovi I, Room 733 - Kassi S. Bailey; Matthew J. Rowe; E. Charles Adams (Archaeological and Anthropological Sciences, 2020)

Carbon:nitrogen ratio as a proxy for tissue nonpolar lipid content and condition in black sea bass Centropristis striata along the Middle Atlantic Bight - Ginni A. La Rosa; Ryan J. Woodland; Christopher L. Rowe (Marine Biology, 2020)

Accounting for Carbon Flux to Mycorrhizal Fungi May Resolve Discrepancies in Forest Carbon Budgets - Andrew P. Ouimette; Scott V. Ollinger; Lucie C. Lepine; Ryan B. Stephens; Rebecca J. Rowe; Matthew A. Vadeboncoeur; Shersingh J. Tumber-Davila; Erik A. Hobbie (Ecosystems, 2020)

The underappreciated role of rodent generalists in fungal spore dispersal networks - Ryan B. Stephens; Rebecca J. Rowe (Ecology, 2020)
Animals are often the primary dispersers of seeds and fungal spores. Specialist species that consume fruits or fungal fruiting bodies (sporocarps) as their main food source are thought to play a more important role in dispersal networks compared to generalist species. However, dispersal networks are often based on occurrence data, overlooking the influence of animal abundance and dispersal effectiveness on network interactions. Using rodent‐mycorrhizal fungi networks, we determined how diet specialization and abundance influence the role of rodent species in dispersing fungal spores in temperate forests of northern New Hampshire, USA. We tracked the interactions of five rodent species and 34 fungal taxa over a 3‐yr period across hardwood, mixed, and softwood forest stands. We accounted for fluctuations in rodent abundance and differences in the number of spores dispersed in rodent scat. Myodes gapperi , a fungal specialist, dispersed a more diverse spore community than rodent generalists and was consistently the most important disperser in forest types with high fungal availability. Nevertheless, during years when generalist species such as Tamias striatus and Peromyscus maniculatus reached high abundance, their relative importance (species strength) in networks approached or even surpassed that of M. gapperi , particularly in forest types where M. gapperi was less common and fungal availability was low. Increased numbers of generalists enhanced network interaction diversity and the number of fungal taxa dispersed, the timing of which was coincident with seedling establishment following masting, a stage when inoculation by mycorrhizal fungi is critical for growth and survival. Our findings suggest that although specialists play key roles in dispersing mycorrhizal fungal spores, generalists play a heretofore underappreciated role.

Rural–urban disparities in colorectal cancer survival and risk among men in Utah: a statewide population-based study - Charles R. Rogers; Brenna E. Blackburn; Matthew Huntington; Karen Curtin; Roland J. Thorpe; Kerry Rowe; John Snyder; Vikrant Deshmukh; Michael Newman; Alison Fraser; Ken Smith; Mia Hashibe (Cancer Causes & Control, 2020)

Signaling from below: rodents select for deeper fruiting truffles with stronger volatile emissions - Ryan B. Stephens; Amy M. Trowbridge; Andrew P. Ouimette; W. Berk Knighton; Erik A. Hobbie; Paul C. Stoy; Rebecca J. Rowe (Ecology, 2020)
Many plant and fungal species use volatile organic compounds (VOCs) as chemical signals to convey information about the location or quality of their fruits or fruiting bodies to animal dispersers. Identifying the environmental factors and biotic interactions that shape fruit selection by animals is key to understanding the evolutionary processes that underpin chemical signaling. Using four Elaphomyces truffle species, we explored the role of fruiting depth, VOC emissions, and protein content in selection by five rodent species. We used stable isotope analysis of nitrogen (δ 15 N) in truffles to estimate fruiting depth, proton‐transfer‐reaction mass spectrometry to determine volatile emission composition, and nitrogen concentrations to calculate digestible protein of truffles. We coupled field surveys of truffle availability with truffle spore loads in rodent scat to determine selection by rodents. Despite presumably easier access to the shallow fruiting species, E. americanus (0.5‐cm depth) and E. verruculosus (2.5‐cm depth), most rodents selected for truffles fruiting deeper in the soil, E. macrosporus (4.1‐cm depth) and E. bartlettii (5.0‐cm depth). The deeper fruiting species had distinct VOC profiles and produced significantly higher quantities of odiferous compounds. Myodes gapperi (southern red‐backed vole), a fungal specialist, also selected for truffles with high levels of digestible protein, E. verruculosus and E. macrosporus . Our results highlight the importance of chemical signals in truffle selection by rodents and suggest that VOCs are under strong selective pressures relative to protein rewards. Strong chemical signals likely allow detection of truffles deep within the soil and reduce foraging effort by rodents. For rodents that depend on fungi as a major food source, protein content may also be important in selecting truffles.

A Holocene record of savanna vegetation dynamics in southern lowland Papua New Guinea - Cassandra Rowe; Bruno David; Jerome Mialanes; Sean Ulm; Fiona Petchey; Samantha Aird; Ian J. McNiven; Matthew Leavesley; Thomas Richards (Vegetation History and Archaeobotany, 2020)

Oceanic islands of Wallacea as a source for dispersal and diversification of murine rodents - Kevin C. Rowe; Anang S. Achmadi; Pierre‐Henri Fabre; John J. Schenk; Scott J. Steppan; Jacob A. Esselstyn (Journal of Biogeography, 2019)
Aim To determine the historical dynamics of colonization and whether the relative timing of colonization predicts diversification rate in the species‐rich, murine rodent communities of Indo‐Australia. Location Indo‐Australian Archipelago including the Sunda shelf of continental Asia, Sahul shelf of continental Australia, the Philippines and Wallacea of Indonesia. Taxon Order Rodentia, Family Muridae. Methods We used a fossil‐calibrated molecular phylogeny and Bayesian biogeographical modelling to infer the frequency and temporal sequence of biogeographical transitions among Sunda, Sahul, the Philippines and Wallacea. We estimated diversification rates for each colonizing lineage using a method‐of‐moments estimator of net diversification and Bayesian mixture model estimates of diversification rate shifts. Results We identified 17 biogeographical transitions, including nine originating from Sunda, seven originating from Sulawesi and broader Wallacea and one originating from Sahul. Wallacea was colonized eight times, the Phillipines five times, Sunda twice and Sahul twice. Net diversification rates ranged from 0.2 to 2.12 species/lineage/My with higher rates in secondary and later colonizers than primary colonizers. The highest rates were in the genus Rattus and their closest relatives, irrespective of colonization history. Main Conclusions Our inferences from murines demonstrate once again the substantial role of islands as sources of species diversity in terrestrial vertebrates of the IAA with most speciation events occurring on islands. Sulawesi and broader Wallacea have been a major source of colonists for both island and continental systems. Crossings of Wallace's Line were more common than subsequent transitions across Lydekker's Line to the east. While speciation following colonization of oceanic archipelagos and large islands is consistent with adaptive radiation theory and ideas regarding ecological opportunity, we did not observe a strong signal of incumbency effects. Rather, subsequent colonists of landmasses radiated unhindered by previous radiations.

Zones of influence for soil organic matter dynamics: A conceptual framework for data and models - Claudia Cagnarini; Eleanor Blyth; Bridget A. Emmett; Chris D. Evans; Robert I. Griffiths; Aidan Keith; Laurence Jones; Inma Lebron; Niall P. McNamara; Jeremy Puissant; Sabine Reinsch; David A. Robinson; et al. (Global Change Biology, 2019)
Soil organic matter (SOM) is an indicator of sustainable land management as stated in the global indicator framework of the United Nations Sustainable Development Goals (SDG Indicator 15.3.1). Improved forecasting of future changes in SOM is needed to support the development of more sustainable land management under a changing climate. Current models fail to reproduce historical trends in SOM both within and during transition between ecosystems. More realistic spatio‐temporal SOM dynamics require inclusion of the recent paradigm shift from SOM recalcitrance as an ‘intrinsic property’ to SOM persistence as an ‘ecosystem interaction’. We present a soil profile, or pedon‐explicit, ecosystem‐scale framework for data and models of SOM distribution and dynamics which can better represent land use transitions. Ecosystem‐scale drivers are integrated with pedon‐scale processes in two zones of influence. In the upper vegetation zone, SOM is affected primarily by plant inputs (above‐ and belowground), climate, microbial activity and physical aggregation and is prone to destabilization. In the lower mineral matrix zone, SOM inputs from the vegetation zone are controlled primarily by mineral phase and chemical interactions, resulting in more favourable conditions for SOM persistence. Vegetation zone boundary conditions vary spatially at landscape scales (vegetation cover) and temporally at decadal scales (climate). Mineral matrix zone boundary conditions vary spatially at landscape scales (geology, topography) but change only slowly. The thicknesses of the two zones and their transport connectivity are dynamic and affected by plant cover, land use practices, climate and feedbacks from current SOM stock in each layer. Using this framework, we identify several areas where greater knowledge is needed to advance the emerging paradigm of SOM dynamics—improved representation of plant‐derived carbon inputs, contributions of soil biota to SOM storage and effect of dynamic soil structure on SOM storage—and how this can be combined with robust and efficient soil monitoring.

Temperature influences on growth of unfished juvenile Northern cod ( Gadus morhua ) during stock collapse - Darrell R. J. Mullowney; George A. Rose; Earl G. Dawe; Sherrylynn Rowe; Gary L. Maillet; Eric J. Pedersen (Fisheries Oceanography, 2019)
This study examined growth of unfished juvenile Northern cod ( Gadus morhua ) off Newfoundland concomitant with stock collapse in the cold early 1990s. Two unpublished data sets were examined, one from collapse‐period trapping sites along the northeast coast of Newfoundland and one from a post‐collapse inshore trawl survey. Cumulative surface and bottom temperatures were significant predictors of growth rates of the young fish with year‐classes born during collapse experiencing slower growth than those born during subsequent warming. Relationships between accrued temperature and growth were consistent across periods, with slow growth of collapse‐period fish reflecting slower accumulation of temperature‐at‐age. Temperature influences were spatially broad‐based with no significant differences in growth rates for fish captured along the entire northeast coast of Newfoundland. Predicted differences in growth rates for collapse versus recovery year‐classes were proportional to cumulative surface temperatures but not cumulative bottom temperatures. Although significant, temperature effects on growth were relatively unimportant at youngest ages. Overall, growth differences between periods were small but large differences occurred between slowest and fastest growing year‐classes. The results suggest initial responses to increasing temperatures were delayed following collapse. We conclude that although temperature was an important determinant of dampened productivity that it alone cannot account for the collapse and slow recovery of the stock. This is the first known study to directly quantitatively link temperature impacts to an unfished component of the Northern cod stock complex during collapse, removing need for implicit assumptions about whether or not cold conditions contributed to the collapse of this iconic fish stock.

Sources of primary production to Arctic bivalves identified using amino acid stable carbon isotope fingerprinting - Audrey G. Rowe; Katrin Iken; Arny L. Blanchard; Diane M. O'Brien; Renate Døving Osvik; Martina Uradnikova; Matthew J. Wooller (Isotopes in Environmental and Health Studies, 2019)

Liver and muscle glycogen oxidation and performance with dose variation of glucose–fructose ingestion during prolonged (3 h) exercise - Andy J. King; John P. O’Hara; Nicola C. Arjomandkhah; Josh Rowe; Douglas J. Morrison; Thomas Preston; Roderick F. G. J. King (European Journal of Applied Physiology, 2019)

Paleomagnetic determination of the age and properties of the 1780–1800 AD dome effusion/collapse episode of Mt. Taranaki, New Zealand - Geoffrey A. Lerner; Shane J. Cronin; Gillian M. Turner; Michael C. Rowe (Bulletin of Volcanology, 2019)

Gait stability in response to platform, belt, and sensory perturbations in young and older adults - S. Roeles; P. J. Rowe; S. M. Bruijn; C. R. Childs; G. D. Tarfali; F. Steenbrink; M. Pijnappels (Medical & Biological Engineering & Computing, 2018)

Effect of cattle exclosures on Columbia Spotted Frog abundance - Michael J. Adams; Christopher A. Pearl; Thierry Chambert; Brome McCreary; Stephanie K. Galvan; Jennifer Rowe (Wetlands Ecology and Management, 2018)

Towards improved practices in Life Cycle Assessment of seafood and other aquatic products - Angel Avadí; Patrik J. G. Henriksson; Ian Vázquez-Rowe; Friederike Ziegler (The International Journal of Life Cycle Assessment, 2018)

Influence of porosity and groundmass crystallinity on dome rock strength: a case study from Mt. Taranaki, New Zealand - Edgar U. Zorn; Michael C. Rowe; Shane J. Cronin; Amy G. Ryan; Lori A. Kennedy; James K. Russell (Bulletin of Volcanology, 2018)

Influence of invasive quagga mussels, phosphorus loads, and climate on spatial and temporal patterns of productivity in Lake Michigan: A biophysical modeling study - Mark D. Rowe; Eric J. Anderson; Henry A. Vanderploeg; Steven A. Pothoven; Ashley K. Elgin; Jia Wang; Foad Yousef (Limnology and Oceanography, 2017)
We applied a three‐dimensional biophysical model to Lake Michigan for the years 2000, 2005, and 2010 to consider the mechanisms controlling spatial and temporal patterns of phytoplankton abundance (chlorophyll a ) and lake‐wide productivity. Model skill was assessed by comparison to satellite‐derived Chl a and field‐measured water quality variables. We evaluated model sensitivity to scenarios of varying mussel filter feeding intensity, tributary phosphorus loads, and warm vs. cool winter‐spring climate scenarios. During the winter‐spring phytoplankton bloom, spatial patterns of Chl a were controlled by variables that influenced surface mixed layer depth: deep mixing reduced net phytoplankton growth through light limitation and by exposing the full water column to mussel filter feeding. Onset of summer and winter stratification promoted higher surface Chl a initially by increasing mean light exposure and by separating the euphotic zone from mussels. During the summer stratified period, areas of relatively high Chl a were associated with coastal plumes influenced by tributary‐derived nutrients and coastal upwelling‐downwelling. While mussels influenced spatial and temporal distribution of Chl a , lake‐wide, annual mean primary production was more sensitive to phosphorus and warm/cool meteorology scenarios than to mussel filter feeding scenarios. Although Chl a and primary production declined over the quagga mussel invasion, our results suggest that increased nutrient loads would increase lake‐wide productivity even in the presence of mussels; however, altered spatial and temporal patterns of productivity caused by mussel filter feeding would likely persist.

Changes in Habitat Availability for Multiple Life Stages of Diamondback Terrapins (Malaclemys terrapin) in Chesapeake Bay in Response to Sea Level Rise - Ryan J. Woodland; Christopher L. Rowe; Paula F. P. Henry (Estuaries and Coasts, 2017)

Incorporating linear programing and life cycle thinking into environmental sustainability decision-making: a case study on anchovy canning industry - I. Garcia-Herrero; J. Laso; M. Margallo; A. Bala; C. Gazulla; P. Fullana-i-Palmer; I. Vázquez-Rowe; A. Irabien; R. Aldaco (Clean Technologies and Environmental Policy, 2017)

The role of ecology, neutral processes and antagonistic coevolution in an apparent sexual arms race - Jennifer C. Perry; Colin J. Garroway; Locke Rowe (Ecology Letters, 2017)
Some of the strongest examples of a sexual ‘arms race’ come from observations of correlated evolution in sexually antagonistic traits among populations. However, it remains unclear whether these cases truly represent sexually antagonistic coevolution; alternatively, ecological or neutral processes might also drive correlated evolution. To investigate these alternatives, we evaluated the contributions of intersex genetic correlations, ecological context, neutral genetic divergence and sexual coevolution in the correlated evolution of antagonistic traits among populations of Gerris incognitus water striders. We could not detect intersex genetic correlations for these sexually antagonistic traits. Ecological variation was related to population variation in the key female antagonistic trait (spine length, a defence against males), as well as body size. Nevertheless, population covariation between sexually antagonistic traits remained substantial and significant even after accounting for all of these processes. Our results therefore provide strong evidence for a contemporary sexual arms race.

Predation of diaspidid scale insects on kiwifruit vines by European earwigs, Forficula auricularia, and steel-blue ladybirds, Halmus chalybeus - David P. Logan; Bridget J. Maher; Christina A. Rowe (BioControl, 2017)

Photobiomodulation-induced changes in a monkey model of Parkinson’s disease: changes in tyrosine hydroxylase cells and GDNF expression in the striatum - Nabil El Massri; Ana P. Lemgruber; Isobel J. Rowe; Cécile Moro; Napoleon Torres; Florian Reinhart; Claude Chabrol; Alim-Louis Benabid; John Mitrofanis (Experimental Brain Research, 2017)

In situ electrochemical enrichment and isolation of a magnetite‐reducing bacterium from a high pH serpentinizing spring - Annette R. Rowe; Miho Yoshimura; Doug E. LaRowe; Lina J. Bird; Jan P. Amend; Kazuhito Hashimoto; Kenneth H. Nealson; Akihiro Okamoto (Environmental Microbiology, 2017)
Summary Serpentinization is a geologic process that produces highly reduced, hydrogen‐rich fluids that support microbial communities under high pH conditions. We investigated the activity of microbes capable of extracellular electron transfer in a terrestrial serpentinizing system known as ‘The Cedars’. Measuring current generation with an on‐site two‐electrode system, we observed daily oscillations in current with the current maxima and minima occurring during daylight hours. Distinct members of the microbial community were enriched. Current generation in lab‐scale electrochemical reactors did not oscillate, but was correlated with carbohydrate amendment in Cedars‐specific minimal media. Gammaproteobacteria and Firmicutes were consistently enriched from lab electrochemical systems on δ‐MnO 2 and amorphous Fe(OH) 3 at pH 11. However, isolation of an electrogenic strain proved difficult as transfer cultures failed to grow after multiple rounds of media transfer. Lowering the bulk pH in the media allowed us to isolate a Firmicutes strain ( Paenibacillus sp .). This strain was capable of electrode and mineral reduction (including magnetite) at pH 9. This report provides evidence of the in situ activity of microbes using extracellular substrates as sinks for electrons at The Cedars, but also highlights the potential importance of community dynamics for supporting microbial life through either carbon fixation, and/or moderating pH stress.

Application of novel analytical ultracentrifuge analysis to solutions of fungal mannans - Richard B. Gillis; Gary G. Adams; David T. M. Besong; Eva Machová; Anna Ebringerová; Arthur J. Rowe; Stephen E. Harding; Trushar R. Patel (European Biophysics Journal, 2017)

Temporal shifts in the saltmarsh–Nelson’s sparrow hybrid zone revealed by replicated demographic and genetic surveys - Jennifer Walsh; W. Gregory Shriver; Maureen D. Correll; Brian J. Olsen; Chris S. Elphick; Thomas P. Hodgman; Rebecca J. Rowe; Kathleen M. O’Brien; Adrienme I. Kovach (Conservation Genetics, 2017)

Performance on the Cogstate Brief Battery Is Related to Amyloid Levels and Hippocampal Volume in Very Mild Dementia - Yen Ying Lim; Victor L. Villemagne; Simon M. Laws; Robert H. Pietrzak; David Ames; Christopher Fowler; Stephanie Rainey-Smith; Peter J. Snyder; Pierrick Bourgeat; Ralph N. Martins; Olivier Salvado; Christopher C. Rowe; et al. (Journal of Molecular Neuroscience, 2016)

Depth and temperature associations of haddock Melanogrammus aeglefinus off southern Newfoundland - R. Rogers; S. Rowe; M. J. Morgan (Journal of Fish Biology, 2016)
Using data collected as part of offshore surveys conducted during 1972–2013, haddock Melanogrammus aeglefinus association patterns with depth and temperature in southern Newfoundland waters, the northern extremity of the species' range in the western Atlantic Ocean, were quantified. They were typically concentrated in the deep warm waters along the narrow shelf slope in North‐west Atlantic Fisheries Organization Divisions 3O and 3P with individuals moving seasonally into the shallow waters of the banks as they warmed. While M. aeglefinus were found over a range of depths and temperatures, they were primarily located at depths deeper and temperatures warmer than the median sampled. Analyses demonstrated that of the two hydrographic variables assessed, temperature was most influential in structuring distribution, with individuals appearing to change depth in order to maintain similar temperature throughout the year. Melanogrammus aeglefinus were found predominantly in temperatures of c. 4–8° C which often represented some of the warmest waters available. Differences in fish‐habitat association patterns in relation to sex or maturity status were not readily apparent from the analyses. Warming conditions off Newfoundland and Labrador in recent years might be predicted to improve local M. aeglefinus productivity.

Genetics of aging bone - Douglas J. Adams; David W. Rowe; Cheryl L. Ackert-Bicknell (Mammalian Genome, 2016)

Risk/Benefit Communication about Food—A Systematic Review of the Literature - L. J. Frewer; A. R. H. Fischer; M. Brennan; D. Bánáti; R. Lion; R. M. Meertens; G. Rowe; M. Siegrist; W. Verbeke; C. M. J. L. Vereijken (Critical Reviews in Food Science and Nutrition, 2016)

Integrating legacy soil phosphorus into sustainable nutrient management strategies for future food, bioenergy and water security - Helen Rowe; Paul J. A. Withers; Peter Baas; Neng Iong Chan; Donnacha Doody; Jeff Holiman; Brent Jacobs; Haigang Li; Graham K. MacDonald; Richard McDowell; Andrew N. Sharpley; Jianbo Shen; et al. (Nutrient Cycling in Agroecosystems, 2016)

Terrestrial runoff boosts phytoplankton in a Mediterranean coastal lagoon, but these effects do not propagate to higher trophic levels - A. Liess; O. Rowe; S. N. Francoeur; J. Guo; K. Lange; A. Schröder; B. Reichstein; R. Lefèbure; A. Deininger; P. Mathisen; C. L. Faithfull (Hydrobiologia, 2016)

Use of a robotic device to measure age-related decline in finger proprioception - Morgan L. Ingemanson; Justin B. Rowe; Vicky Chan; Eric T. Wolbrecht; Steven C. Cramer; David J. Reinkensmeyer (Experimental Brain Research, 2016)

Guidelines for Using Movement Science to Inform Biodiversity Policy - Philip S. Barton; Pia E. Lentini; Erika Alacs; Sana Bau; Yvonne M. Buckley; Emma L. Burns; Don A. Driscoll; Lydia K. Guja; Heini Kujala; José J. Lahoz-Monfort; Alessio Mortelliti; Ran Nathan; et al. (Environmental Management, 2015)

Scale effects on the pattern and predictors of small mammal diversity along a local elevational gradient in the Great Basin - Rebecca J. Rowe; Lawrence R. Heaney; Eric A. Rickart (Journal of Biogeography, 2015)
Aim Evaluation of the generality of the diversity–elevation relationship has highlighted effects of scale (spatial extent and grain size) on pattern perception. In contrast, the effects of scale on the attribution of drivers of diversity along elevational gradients remain largely unexplored. This is important because many causal factors have been proposed, and remotely sensed data about abiotic factors are available at increasingly fine grain sizes. Here, we evaluate the effects both of the resolution of the species diversity estimate on the pattern perceived, and of environmental predictor grain size on the potential contribution to each pattern. Location Ruby Mountains, Nevada, western North America. Methods For the small mammal fauna along one local elevational gradient, we compared patterns among estimates of richness derived from site‐based occurrences rarefied by survey effort and those inferred from interpolation across species’ elevational ranges. Using an information‐theoretic approach, we evaluated the relative importance of spatial and environmental factors in structuring each richness distribution. Climate and habitat were assessed at coarse and fine grain sizes. Comparisons were based on model fit and relative variable importance. Results We find general congruence in the diversity–elevation relationship, with peak diversity near the midpoint of the sampled gradient. Despite this commonality in pattern, we find the attribution of underlying drivers is substantially influenced by the type of richness estimate and by the grain size of the predictor variables. Main conclusions Our results illustrate that the factors identified as predictors of diversity can be sensitive to grain size, and that this sensitivity is not equally apparent under different measures of richness obtained from the same survey data. We call for broader discussion of scale effects and resolution appropriateness for elevational diversity gradients. This is particularly important because mismatches in scale may result in misguided conservation or management initiatives.

Terrestrial runoff may reduce microbenthic net community productivity by increasing turbidity: a Mediterranean coastal lagoon mesocosm experiment - A. Liess; C. Faithfull; B. Reichstein; O. Rowe; J. Guo; R. Pete; G. Thomsson; W. Uszko; S. N. Francoeur (Hydrobiologia, 2015)

Comparison of stormwater runoff from sedum, native prairie, and vegetable producing green roofs - Leigh J. Whittinghill; D. Bradley Rowe; Jeffery A. Andresen; Bert M. Cregg (Urban Ecosystems, 2015)

Replenishment of volatile-rich mafic magma into a degassed chamber drives mixing and eruption of Tungurahua volcano - Madison L. Myers; Dennis J. Geist; Michael C. Rowe; Karen S. Harpp; Paul J. Wallace; Josef Dufek (Bulletin of Volcanology, 2014)

Time flies when you are in a groove: using entrainment to mechanical resonance to teach a desired movement distorts the perception of the movement’s timing - Daniel K. Zondervan; Jaime E. Duarte; Justin B. Rowe; David J. Reinkensmeyer (Experimental Brain Research, 2014)

MultiSig: a new high-precision approach to the analysis of complex biomolecular systems - Richard B. Gillis; Gary G. Adams; Thomas Heinze; Melanie Nikolajski; Stephen E. Harding; Arthur J. Rowe (European Biophysics Journal, 2013)

Continental‐scale assessment of genetic diversity and population structure in quaking aspen ( P opulus tremuloides ) - Colin M. Callahan; Carol A. Rowe; Ronald J. Ryel; John D. Shaw; Michael D. Madritch; Karen E. Mock (Journal of Biogeography, 2013)
Aim Quaking aspen ( P opulus tremuloides ) has the largest natural distribution of any tree native to North America. The primary objectives of this study were to characterize range‐wide genetic diversity and genetic structuring in quaking aspen, and to assess the influence of glacial history and rear‐edge dynamics. Location North America. Methods Using a sample set representing the full longitudinal and latitudinal extent of the species’ distribution, we examined geographical patterns of genetic diversity and structuring using 8 nuclear microsatellite loci in 794 individuals from 30 sampling sites. Results Two major genetic clusters were identified across the range: a south‐western cluster and a northern cluster. The south‐western cluster, which included two subclusters, was bounded approximately by the Continental Divide to the east and the southern extent of the ice sheet at the Last Glacial Maximum to the north. Subclusters were not detected in the northern cluster, despite its continent‐wide distribution. Genetic distance was significantly correlated with geographical distance in the south‐western but not the northern cluster, and allelic richness was significantly lower in south‐western sampling sites compared with northern sampling sites. Population structuring was low overall, but elevated in the south‐western cluster. Main conclusions Aspen populations in the south‐western portion of the range are consistent with expectations for a historically stable edge, with low within‐population diversity, significant geographical population structuring, and little evidence of northward expansion. Structuring within the south‐western cluster may result from distinct gene pools separated during the Pleistocene and reunited following glacial retreat, similar to patterns found in other forest tree species in the western USA . In aspen, populations in the south‐western portion of the species range are thought to be at particularly high risk of mortality with climate change. Our findings suggest that these same populations may be disproportionately valuable in terms of both evolutionary potential and conservation value.

The distribution and host range of Batrachochytrium dendrobatidis in New Zealand, 1930–2010 - Stephanie D. Shaw; Lee F. Skerratt; Amanada Haigh; Ben D. Bell; Lisa Daglish; Phillip J. Bishop; Rachel Summers; Virginia Moreno; Sabine Melzer; Michel Ohmer; Sarah Herbert; Dianne Gleeson; et al. (Ecology, 2013)
Chytridiomycosis caused by the fungal invasive pathogen Batrachochytrium dendrobatidis (Bd) was first detected in 1999 in Christchurch, New Zealand, in the Australian introduced frog species Litoria raniformis . It was detected in wild native frogs in the critically endangered Leiopelma archeyi in 2001 on the Coromandel Peninsula and has been suggested as responsible for a mass decline (88%) in that population between 1994 and 2002. We report the current distribution, host species and prevalence, where known, of Bd in New Zealand, which is essential for conservation management of New Zealand native frogs ( Leiopelma spp.). The data set is structured so that it can be readily added to the Australian Bd database for further analyses. Our data included all regions in New Zealand and six offshore islands at 135 sites with 704 records from 23 contributors spanning collection dates 1930–2010. We report 54 positive sites from 132 positive individuals. We also detail negative findings, but declaring an area free from disease should consider the sensitivity of the test used and numbers of individuals tested. The data also included a comprehensive museum survey testing 152 individuals from five species (20 L. archeyi , 50 L. hochstetteri , 15 L. aurea , 40 L. ewingii, and 27 L. raniformis ) from 1930–1999 using histology and Bd‐specific immunohistochemistry. All museum specimens were negative, so the 1999 positive result is still the earliest record. In the L. archeyi Coromandel Ranges population, the period prevalence of Bd from 2006 to 2010 was relatively stable at 16%, but the number of animals tested remains low (up to N = 19) due to the now depleted population numbers. The period prevalence of Bd in the L. archeyi Whareorino population has remained both consistent and low (6%) between 2005 and 2010. In L. hochstetteri , L. hamiltoni, and L. pakeka all sampling for Bd has been negative. Positive Bd results have been found in all three Litoria spp., but Bd has not been found in the six offshore areas tested. Most data have been previously unpublished and represent the first confirmed reports of Bd in many regions and species in New Zealand.

Recent advances in 2D and 3D in vitro systems using primary hepatocytes, alternative hepatocyte sources and non-parenchymal liver cells and their use in investigating mechanisms of hepatotoxicity, cell signaling and ADME - Patricio Godoy; Nicola J. Hewitt; Ute Albrecht; Melvin E. Andersen; Nariman Ansari; Sudin Bhattacharya; Johannes Georg Bode; Jennifer Bolleyn; Christoph Borner; Jan Böttger; Albert Braeuning; Robert A. Budinsky; et al. (Archives of Toxicology, 2013)

Do surf zones in New Jersey provide “nursery” habitat for southern fishes? - Kenneth W. Able; Mark J. Wuenschel; Thomas M. Grothues; James M. Vasslides; Peter M. Rowe (Environmental Biology of Fishes, 2013)

Cryptic genetic diversity in Rattus of the San Francisco Bay region, California - Chris J. Conroy; Kevin C. Rowe; Karen M. C. Rowe; Pauline L. Kamath; Ken P. Aplin; Lucia Hui; David K. James; Craig Moritz; James L. Patton (Biological Invasions, 2013)

High-resolution radiocarbon dating of marine materials in archaeological contexts: radiocarbon marine reservoir variability between Anadara, Gafrarium, Batissa, Polymesoda spp. and Echinoidea at Caution Bay, Southern Coastal Papua New Guinea - Fiona Petchey; Sean Ulm; Bruno David; Ian J. McNiven; Brit Asmussen; Helene Tomkins; Nic Dolby; Ken Aplin; Thomas Richards; Cassandra Rowe; Matthew Leavesley; Herman Mandui (Archaeological and Anthropological Sciences, 2013)

High rate of prey consumption in a small predatory fish on coral reefs - W. E. Feeney; O. M. Lönnstedt; Y. Bosiger; J. Martin; G. P. Jones; R. J. Rowe; M. I. McCormick (Coral Reefs, 2012)

Size increase in high elevation ground squirrels over the last century - Lindsey M. Eastman; Toni Lyn Morelli; Kevin C. Rowe; Chris J. Conroy; Craig Moritz (Global Change Biology, 2012)
There is increasing evidence for morphological change in response to recent environmental change, but how this relates to fluctuations in geographic range remains unclear. We measured museum specimens from two time periods (1902–1950 and 2000–2008) that vary significantly in climate to assess if and how two high elevation contracting species of ground squirrels in the Sierra Nevada of California, Belding's ground squirrel ( Urocitellus beldingi ) and the golden‐mantled ground squirrel ( Callospermophilus lateralis ), and one lower elevation, stable species, the California ground squirrel ( Otospermophilus beecheyi ), have responded morphologically to changes over the last century. We measured skull length (condylobasal length), an ontogenetically more labile trait highly correlated with body size, and maxillary toothrow length, a more developmentally constrained trait predictive of skull shape. C. lateralis and U. beldingi , both obligate hibernators, have increased in body size, but have not changed in shape. In contrast, O. beecheyi , which only hibernates in parts of its range, has shown no significant change in either morphometric trait. The increase in body size in the higher elevation species, hypothesized to be a plastic effect due to a longer growing season and thus prolonged food availability, opposes the expected direction of selection for decreased body size under chronic warming. Our study supports that population contraction is related to physiological rather than nutritional constraints.

Impacts of atmospheric nitrogen deposition: responses of multiple plant and soil parameters across contrasting ecosystems in long‐term field experiments - Gareth K. Phoenix; Bridget A. Emmett; Andrea J. Britton; Simon J. M. Caporn; Nancy B. Dise; Rachel Helliwell; Laurence Jones; Jonathan R. Leake; Ian D. Leith; Lucy J. Sheppard; Alwyn Sowerby; Michael G. Pilkington; et al. (Global Change Biology, 2012)
Atmospheric nitrogen ( N ) deposition is a global and increasing threat to biodiversity and ecosystem function. Much of our current understanding of N deposition impacts comes from field manipulation studies, although interpretation may need caution where simulations of N deposition (in terms of dose, application rate and N form) have limited realism. Here, we review responses to simulated N deposition from the UKREATE network, a group of nine experimental sites across the UK in a diversity of heathland, grassland, bog and dune ecosystems which include studies with a high level of realism and where many are also the longest running globally on their ecosystem type. Clear responses were seen across the sites with the greatest sensitivity shown in cover and species richness of bryophytes and lichens. Productivity was also increased at sites where N was the limiting nutrient, while flowering also showed high sensitivity, with increases and declines seen in dominant shrub and forb species, respectively. Critically, these parameters were responsive to some of the lowest additional loadings of N (7.7–10 kg ha −1 yr −1 ) showing potential for impacts by deposition rates seen in even remote and ‘unpolluted’ regions of E urope. Other parameters were less sensitive, but nevertheless showed response to higher doses. These included increases in soil % N and ‘plant available’ KCl extractable N , N cycling rates and acid–base status. Furthermore, an analysis of accumulated dose that quantified response against the total N input over time suggested that N impacts can ‘build up’ within an ecosystem such that even relatively low N deposition rates can result in ecological responses if continued for long enough. Given the responses have important implications for ecosystem structure, function, and recovery from N loading, the clear evidence for impacts at relatively low N deposition rates across a wide range of habitats is of considerable concern.

Salt tolerance of common green roof and green wall plants - Leigh J. Whittinghill; D. Bradley Rowe (Urban Ecosystems, 2011)

Near-Surface Larval and Juvenile Fish in Coastal Habitats: Comparisons Between the Inner Shelf and an Estuary in the New York Bight During Summer and Fall - Kenneth W. Able; Thomas M. Grothues; Peter M. Rowe; Mark J. Wuenschel; James M. Vasslides (Estuaries and Coasts, 2011)

Environmental change and declining resource availability for small‐mammal communities in the Great Basin - Rebecca J. Rowe; Rebecca C. Terry; Eric A. Rickart (Ecology, 2011)
Changes in climate and land use can impact natural systems across all levels of ecological organization. Most documented and anticipated effects consider species' properties, including phenologies, geographic distributions, and abundances. Responses of higher‐level aggregate community or ecosystem properties have not been considered as they are assumed to be relatively stable due to compensatory dynamics and diversity–stability relationships. However, this assumption may not be as fundamental as previously thought. Here we assess stability in the aggregate properties of total abundance, biomass, and energy consumption for small‐mammal communities in the Great Basin, using paired historical and modern survey data spanning nearly a century of environmental change. Results show marked declines in each aggregate property independent of spatial scale, elevation, or habitat type, and a reallocation of available biomass and energy favoring diet and habitat generalists. Because aggregate properties directly reflect resource availability, our findings indicate a regionwide decline in resources of ∼50% over the past century, which may signal a resource crisis. This work illustrates the power of using aggregate properties as indicators of ecological conditions and environmental change at broad spatial and temporal scales.

Poly(T) Variation in Heteroderid Nematode Mitochondrial Genomes is Predominantly an Artefact of Amplification - Angelique H. Riepsamen; Tracey Gibson; Janet Rowe; David J. Chitwood; Sergei A. Subbotin; Mark Dowton (Journal of Molecular Evolution, 2011)

Range dynamics of small mammals along an elevational gradient over an 80‐year interval - REBECCA J. ROWE; JOHN A. FINARELLI; ERIC A. RICKART (Global Change Biology, 2010)
One expected response to observed global warming is an upslope shift of species elevational ranges. Here, we document changes in the elevational distributions of the small mammals within the Ruby Mountains in northeastern Nevada over an 80‐year interval. We quantified range shifts by comparing distributional records from recent comprehensive field surveys (2006–2008) to earlier surveys (1927–1929) conducted at identical and nearby locations. Collector field notes from the historical surveys provided detailed trapping records and locality information, and museum specimens enabled confirmation of species' identifications. To ensure that observed shifts in range did not result from sampling bias, we employed a binomial likelihood model (introduced here) using likelihood ratios to calculate confidence intervals around observed range limits. Climate data indicate increases in both precipitation and summer maximum temperature between sampling periods. Increases in winter minimum temperatures were only evident at mid to high elevations. Consistent with predictions of change associated with climate warming, we document upslope range shifts for only two mesic‐adapted species. In contrast, no xeric‐adapted species expanded their ranges upslope. Rather, they showed either static distributions over time or downslope contraction or expansion. We attribute these unexpected findings to widespread land‐use driven habitat change at lower elevations. Failure to account for land‐use induced changes in both baseline assessments and in predicting shifts in species distributions may provide misleading objectives for conservation policies and management practices.

Temporal production of the two Bacillus anthracis siderophores, petrobactin and bacillibactin - Melissa K. Wilson; Rebecca J. Abergel; Jean E. L. Arceneaux; Kenneth N. Raymond; B. Rowe Byers (BioMetals, 2010)

Structure and heterogeneity of gliadin: a hydrodynamic evaluation - Shirley Ang; Jana Kogulanathan; Gordon A. Morris; M. Samil Kök; Peter R. Shewry; Arthur S. Tatham; Gary G. Adams; Arthur J. Rowe; Stephen E. Harding (European Biophysics Journal, 2010)

Genetic analysis of avian influenza A viruses isolated from domestic waterfowl in live-bird markets of Hanoi, Vietnam, preceding fatal H5N1 human infections in 2004 - Samadhan J. Jadhao; Doan C. Nguyen; Timothy M. Uyeki; Michael Shaw; Taronna Maines; Thomas Rowe; Catherine Smith; Lien P. T. Huynh; Ha K. Nghiem; Diep H. T. Nguyen; Hang K. L. Nguyen; Hanh H. T. Nguyen; et al. (Archives of Virology, 2009)

Application of the probability-based Maryland Biological Stream Survey to the state’s assessment of water quality standards - Mark T. Southerland; Jon H. Vølstad; Edward D. Weber; Ronald J. Klauda; Charles A. Poukish; Matthew C. Rowe (Environmental Monitoring and Assessment, 2009)

Elevational gradients and species richness: do methods change pattern perception? - Rebecca J. Rowe; Scott Lidgard (Global Ecology and Biogeography, 2009)
Aim Species richness patterns along elevational gradients have been documented extensively. Yet, the implications of differences in how the data are compiled are seldom explored. We investigate the effect of grain size on the richness–elevation relationship. Grain size varies among the principal methods used to collect or aggregate species occurrences: localized sites, elevational ‘bins’ and interpolation of species ranges. Assumptions of sampling and species distributions also vary among these methods. Methodology can influence the pattern that is perceived and comparability of results. We compare patterns from all three methods explicitly using the same suite of observations, based on museum records and field surveys of non‐flying small mammals. Our assessment is enhanced by comparing patterns resulting from each method for each of six adjacent mountain ranges. Location Utah, North America. Methods We document elevational species richness patterns using generalized linear models (GLMs), comparing the general shape of the trend as well as curvature, location and magnitude of peak richness across methods, both within and among gradients. We also introduce a new procedure to test for richness peaks using site‐based occurrences. Results We find a general congruence of the richness–elevation relationship, depicting a hump‐shaped pattern with a second‐order polynomial GLM showing a significant fit to nearly all gradient‐methodology combinations. However, underlying characteristics of the trend may vary with grain size. As grain size coarsens, maximum species richness increases and elevation of the mode slightly decreases. Results for curvature vary, but degree of curvature tends to increase as grain size coarsens. The richness–elevation patterns are independent of sampling effects. Main conclusions The perceived elevational diversity pattern for small mammals along these mountain ranges is not scale‐dependent. Differences in how the data are compiled are not reflected in major differences in patterns, even when local samples are neither uniformly spaced nor sampled with the same intensity. This result lends confidence to the assertion that patterns documented in similar studies with different methodologies and for which sampling is sufficiently comprehensive are good indicators of diversity. However, consistency of results from more than one compilation method may help to address issues of scale‐dependence, more so when these comparisons are made explicit.

Galantamine-induced improvements in cognitive function are not related to alterations in α4β2 nicotinic receptors in early Alzheimer’s disease as measured in vivo by 2-[18F]Fluoro-A-85380 PET - J. R. Ellis; P. J. Nathan; V. L. Villemagne; R. S. Mulligan; T. Saunder; K. Young; C. L. Smith; J. Welch; M. Woodward; K. A. Wesnes; G. Savage; C. C. Rowe (Psychopharmacology, 2009)

Robust planning for restoring diadromous fish species in New Zealand's lowland rivers and streams - J.R. Leathwick; J. Elith; D. Rowe; K. Julian (New Zealand Journal of Marine and Freshwater Research, 2009)
We used statistical models to predict the distributions of 15 native diadromous fish species across New Zealand's river and stream network, and demonstrate their potential use for guiding the restoration of freshwater ecosystems. Models were fitted to an extensive collection of field samples describing the distributions of individual fish species, coupled with a set of environmental predictors chosen primarily for their functional relevance to diadromous fish species. Models were fitted to observations of species occurrence using boosted regression trees (BRT), an advanced regression technique that combines excellent predictive performance with good description of relationships between species occurrence and individual environmental predictors. Environment‐based predictions of species distributions were then made for all river and stream segments. We explored the use of these predictions to guide the selection of sites where diadromous species are likely to occur, and to set restoration targets, once a restoration site has been selected. Descriptions of the environmental preferences of the different species, based on relationships revealed by the statistical models, provide important clues to the likely responses of species to restoration of favourable environmental conditions, e.g., by restoring riparian shade and/or when reinstating access to/from the sea.

Abundance and demography of bottlenose dolphins in Dusky Sound, New Zealand, inferred from dorsal fin photographs - Rohan J. C. Currey; Lucy E. Rowe; Stephen M. Dawson; Elisabeth Slooten (New Zealand Journal of Marine and Freshwater Research, 2008)
The bottlenose dolphins ( Tursiops truncatus ) of Dusky Sound, Fiordland, New Zealand are a little‐studied group at the southern limit of the species range. Conducting a photo‐identification census and capture‐recapture analyses, we estimated there were 102 (CV = 0.9%) bottlenose dolphins in Dusky Sound during summer 2007/08, the first abundance estimate for this population. We did not encounter individuals from Doubtful Sound in Dusky Sound, suggesting little or no interchange between these neighbouring populations. Using a sex‐prediction model derived from laser‐metric photographs of dolphins in Doubtful Sound, we predicted the sexes of 79 individuals (98–99% of adults and sub‐adults) in Dusky Sound. Our predictions provided a sex ratio of 35 males to 44 females, not significantly different to a 1:1 ratio (G = 1.02, P > 0.05). High resighting rates of individual dolphins suggest the population may be resident, with dolphins observed throughout the entire fiord system.

Clonal dynamics in western North American aspen ( Populus tremuloides ) - K. E. MOCK; C. A. ROWE; M. B. HOOTEN; J. DEWOODY; V. D. HIPKINS (Molecular Ecology, 2008)
Clonality is a common phenomenon in plants, allowing genets to persist asexually for much longer periods of time than ramets. The relative frequency of sexual vs. asexual reproduction determines long‐term dominance and persistence of clonal plants at the landscape scale. One of the most familiar and valued clonal plants in North America is aspen ( Populus tremuloides ). Previous researchers have suggested that aspen in xeric landscapes of the intermountain west represent genets of great chronological age, maintained via clonal expansion in the near absence of sexual reproduction. We synthesized microsatellite data from 1371 ramets in two large sampling grids in Utah. We found a surprisingly large number of distinct genets, some covering large spatial areas, but most represented by only one to a few individual ramets at a sampling scale of 50 m. In general, multi‐ramet genets were spatially cohesive, although some genets appear to be fragmented remnants of much larger clones. We conclude that recent sexual reproduction in these landscapes is a stronger contributor to standing genetic variation at the population level than the accumulation of somatic mutations, and that even some of the spatially large clones may not be as ancient as previously supposed. Further, a striking majority of the largest genets in both study areas had three alleles at one or more loci, suggesting triploidy or aneuploidy. These genets tended to be spatially clustered but not closely related. Together, these findings substantially advance our understanding of clonal dynamics in western North American aspen, and set the stage for a broad range of future studies.

Evolution of biological dispersal corridors through a tectonically active mountain range in New Zealand - D. Craw; C. P. Burridge; P. Upton; D. L. Rowe; J. M. Waters (Journal of Biogeography, 2008)
Aim To assess the geological evolution and biogeographical implications of low mountain passes. In particular, we question the common biogeographical belief that major mountain belts form impervious physical barriers to biological dispersal, and that related taxa found on opposites sides of mountains are necessarily a result of vicariant tectonic processes. Location The Southern Alps of New Zealand form a long (500 km) narrow mountain belt at the oblique collisional Pacific–Australian tectonic plate boundary. High mountains were uplifted during the Pliocene (2–5 Ma) and uplift has continued to the present day. Methods We integrate previous work from several disciplines to obtain an overview of inter‐relationships between plate tectonic processes, geomorphology and biogeography along the main mountain barrier in New Zealand, and then extend this approach to other major mountain belts. Results The Southern Alps initially formed a barrier to at least some biological dispersal, including vicariant formation of separate species of freshwater non‐migratory galaxiid fish on either side. However, the high mountain barrier was breached in several places when passive transport of topography occurred, from the low‐erosion rain shadow on the eastern side towards the high‐erosion, high‐rainfall western side. This tectonic transport resulted in the capture of eastern rivers by west‐draining rivers, leaving low passes at the topographic divide. These low‐elevation corridors permitted biological dispersal across the mountains, although continued uplift raises these passes. A new set of passes has formed in the northern part of the mountains where younger faults are cutting across the older mountain topography. These potential dispersal corridors are becoming lower with continued erosion, and more common as the defining structures migrate southwards. Main conclusions Biological dispersal across the Southern Alps may be facilitated by numerous mountain passes, especially via the new passes formed by cross‐cutting faults. More low‐lying corridors existed than is readily apparent now, as old river capture‐related passes have been blocked by ongoing uplift. The dynamic mountain‐building and erosional environment typified by the Southern Alps occurs in all the world’s collisional mountain belts, such as the Andes, Himalayas, European Alps and North American Cordillera. Sister taxa occurring across mountain belts are not necessarily a result of vicariance driven by the rise of the mountains, as numerous passes may have permitted intermittent dispersal. The evolution of low passes may have been more prevalent than is currently appreciated, suggesting that topographically complex mountain ranges might be more effectively viewed as dynamic filters within a probability landscape rather than as static and impervious high‐altitude barriers to all but the rarest of biological dispersal events. In some cases, the biological disjunctions observed across mountains may more directly reflect habitat differentiation driven by orographic mountain development that has limited the probability of trans‐alpine dispersal success.

Dispersal, disturbance and the contrasting biogeographies of New Zealand’s diadromous and non‐diadromous fish species - J. R. Leathwick; J. Elith; W. L. Chadderton; D. Rowe; T. Hastie (Journal of Biogeography, 2008)
Aim To examine the relationship between diadromy and dispersal ability in New Zealand’s freshwater fish fauna, and how this affects the current environmental and geographic distributions of both diadromous and non‐diadromous species. Location New Zealand. Methods Capture data for 15 diadromous and 15 non‐diadromous fish species from 13,369 sites throughout New Zealand were analysed to establish features of their geographic ranges. Statistical models were used to determine the main environmental correlates of species’ distributions, and to establish the environmental conditions preferred by each species. Environmental predictors, chosen for their functional relevance, were derived from an extensive GIS database describing New Zealand’s river and stream network. Results In terms of geography, most diadromous species occur in a scattered fashion throughout extensive geographic ranges, and occupy large numbers of catchments of widely varying size. By contrast, most non‐diadromous species show relatively high levels of occupancy of smaller geographic ranges, and most are restricted to a few large catchments, particularly in the eastern South Island. In terms of environment, there is marked separation of diadromous from non‐diadromous species, with diadromous species generally caught most frequently in low‐gradient coastal rivers and streams with warm, maritime climates. With a few notable exceptions, most diadromous species have lower occurrence in river segments that are located above obstacles to upstream migration. Non‐diadromous species are usually caught in inland rivers and streams with cool, strongly seasonal climates, typified by a low frequency of high‐intensity rainfall events. Main conclusions We interpret the contrasting biogeographies of New Zealand’s diadromous and non‐diadromous species as reflecting interaction between their marked differences in dispersal ability and a landscape that is subject to recurrent, often large‐scale, natural disturbance. While both groups are likely to be equally susceptible to local, disturbance‐driven extinction, the much greater dispersal ability of diadromous species has allowed them to persist over wide geographic ranges. By contrast, the distributions of most non‐diadromous species are concentrated in a few large catchments, mostly in regions where less intense natural disturbance regimes are likely to have favoured their survival.

Changes in fire regimes since the Last Glacial Maximum: an assessment based on a global synthesis and analysis of charcoal data - M. J. Power; J. Marlon; N. Ortiz; P. J. Bartlein; S. P. Harrison; F. E. Mayle; A. Ballouche; R. H. W. Bradshaw; C. Carcaillet; C. Cordova; S. Mooney; P. I. Moreno; et al. (Climate Dynamics, 2008)

A link between sound producing musculature and mating success in Atlantic cod - S. Rowe; J. A. Hutchings (Journal of Fish Biology, 2008)
Individual variability in the mating success of male Atlantic cod Gadus morhua was quantified within an aggregation ( n = 59) breeding undisturbed in a large (684 m 3 ) mesocosm tank. Observational and morphometric data were examined to assess the degree to which this mating variation could be explained by aspects of morphology, condition and spawning behaviour. The number of ventral mounts initiated ( i.e. mating success) was highly variable; most mounts were initiated by a very small percentage of available males. The significant correlate of male mating success was mass of the sound producing musculature, i.e. drumming muscles. Neither body size, condition, pelvic and median fin morphology nor aggression influenced the number of ventral mounts initiated by a male. The present study suggests a possible link between sound production and mating success in Atlantic cod.

Life at low temperatures: A novel breeding‐system adjustment in a polar cladoceran - Paul D. N. Hebert; Chad L. Rowe; Sarah J. Adamowicz (Limnology and Oceanography, 2007)
The typical breeding system of cladocerans, cyclic parthenogenesis, is poorly suited to polar settings because it requires one or more rounds of parthenogenesis before the production of males and sexual eggs. Past work has shown that many arctic cladocerans have secondarily made the transition to obligate, apomictic parthenogenesis. Arctic populations of Holopedium gibberum lack males, suggesting their possible adoption of this breeding system. However, this study shows that these lineages instead possess genotypic characteristics expected under either self‐fertilization or automictic parthenogenesis, the first record of such a breeding system in the Cladocera. As populations of Holopedium from southerly areas reproduce by cyclic parthenogenesis, this breeding system transition appears to represent an adaptive response to living at low temperatures.

Social and ecological factors affecting paternity allocation in American robins with overlapping broods - Karen M. C. Rowe; Patrick J. Weatherhead (Behavioral Ecology and Sociobiology, 2007)

Defining population boundaries: use of three Bayesian approaches with microsatellite data from British natterjack toads ( Bufo calamita ) - G. ROWE; T. J. C. BEEBEE (Molecular Ecology, 2007)
Defining boundaries between populations is often difficult in the absence of information about current levels of gene flow. Such definitions can be important, however, both for the understanding of population dynamics and for conservation planning. Recently developed Bayesian methods for analysing genetic data now provide a powerful approach to this problem. Natterjack toads Bufo calamita are endangered in Britain, where their distribution is restricted to four geographically discrete regions. In three of these regions the boundaries between populations are often uncertain. We therefore used Bayesian approaches with microsatellite data to try and define British natterjack population structure, and thus inform conservation management. A large sample of natterjack toads from all 38 locations in Britain where the species is native was genotyped at eight microsatellite loci. The genetic diversity of natterjack populations declined as a function of increasing latitude, echoing postglacial colonization dynamics. Comparisons of three assignment methods ( structure , baps and geneland ) generated some broad similarities but also some inconsistencies in the definitions of population structure, especially in the most complex region (south Cumbria). Implications of the analyses for the future conservation of Bufo calamita in Britain are discussed.

Defining population boundaries: use of three Bayesian approaches with microsatellite data from British natterjack toads (Bufo calamita) - G. ROWE; T. J. C. BEEBEE (Molecular Ecology, 2007)

Vegetation Type Affects the Relationship Between Soil Carbon to Nitrogen Ratio and Nitrogen Leaching - E. C. Rowe; C. D. Evans; B. A. Emmett; B. Reynolds; R. C. Helliwell; M. C. Coull; C. J. Curtis (Water, Air, & Soil Pollution, 2006)

Comparative phylogeography of eastern chipmunks and white‐footed mice in relation to the individualistic nature of species - KEVIN C. ROWE; EDWARD J. HESKE; KEN N. PAIGE (Molecular Ecology, 2006)
Palaeoecological studies have demonstrated that ecological communities as a whole did not remain stable throughout the climatic fluctuations of the Quaternary. The result is that long‐term associations of species cannot be inferred by contemporary associations in ecological communities. Therefore, the evolutionary significance of any contemporary ecological interactions among species and of the biotic community within which species have evolved also cannot be assumed from contemporary conditions. Comparative phylogeographic data provide a method to identify species within ecological communities that have shared biogeographic histories. We present an example of a long‐term association between populations of two mammalian species, eastern chipmunks ( Tamias striatus ) and white‐footed mice ( Peromyscus leucopus ), which are commonly associated with deciduous forest habitats. The distribution of mitochondrial DNA variation in T. striatus and P. leucopus from previously glaciated regions of the eastern United States support the hypothesis that, in at least part of their range, genetic lineages of the two species have expanded from similar population sources since the Last Glacial Maximum. In addition, the spatial concordance of genetic lineages of T. striatus and P. leucopus with the oak‐savannah forest formations of Wisconsin and Illinois, suggest that populations associated with this community colonized the area in association with a set of arboreal species that comprise their deciduous forest habitat.

The mobA Gene Is Required for Assimilatory and Respiratory Nitrate Reduction but not Xanthine Dehydrogenase Activity in Pseudomonas aeruginosa - Chris Noriega; Daniel J. Hassett; John J. Rowe (Current Microbiology, 2005)

Elevational gradient analyses and the use of historical museum specimens: a cautionary tale - Rebecca J. Rowe (Journal of Biogeography, 2005)
Aim The value of biodiversity informatics rests upon the capacity to assess data quality. Yet as these methods have developed, investigating the quality of the underlying specimen data has largely been neglected. Using an exceptionally large, densely sampled specimen data set for non‐flying small mammals of Utah, I evaluate measures of uncertainty associated with georeferenced localities and illustrate the implications of uncritical incorporation of data in the analysis of patterns of species richness and species range overlap along elevational gradients. Location Utah, USA, with emphasis on the Uinta Mountains. Methods Employing georeferenced specimen data from the Mammal Networked Information System (MaNIS), I converted estimates of areal uncertainty into elevational uncertainty using a geographic information system (GIS). Examining patterns in both areal and elevational uncertainty measures, I develop criteria for including localities in analyses along elevational gradients. Using the Uinta Mountains as a test case, I then examine patterns in species richness and species range overlap along an elevational gradient, with and without accounting for data quality. Results Using a GIS, I provide a framework for post‐hoc 3‐dimensional georeferencing and demonstrate collector‐recorded elevations as a valuable technique for detecting potential errors in georeferencing. The criteria established for evaluating data quality when analysing patterns of species richness and species range overlap in the Uinta Mountains test case reduced the number of localities by 44% and the number of associated specimens by 22%. Decreasing the sample size in this manner resulted in the subsequent removal of one species from the analysis. With and without accounting for data quality, the pattern of species richness along the elevational gradient was hump‐shaped with a peak in richness at about mid‐elevation, between 2300 and 2600 m. In contrast, the frequencies of different pair‐wise patterns of elevational range overlap among species differed significantly when data quality was and was not accounted for. Main conclusions These results indicate that failing to assess spatial error in data quality did not alter the shape of the observed pattern in species richness along the elevational gradient nor the pattern of species’ first and last elevational occurrences. However, it did yield misleading estimates of species richness and community composition within a given elevational interval, as well as patterns of elevational range overlap among species. Patterns of range overlap among species are often used to infer processes underlying species distributions, suggesting that failure to account for data quality may alter interpretations of process as well as perceived patterns of distribution. These results illustrate that evaluating the quality of the underlying specimen data is a necessary component of analyses incorporating biodiversity informatics.

Neglected native or undesirable alien? Resolution of a conservation dilemma concerning the pool frog Rana lessonae - Trevor J. C. Beebee; John Buckley; Ivor Evans; Jim P. Foster; Antony H. Gent; Chris P. Gleed-Owen; Geoffrey Kelly; Graham Rowe; Charles Snell; Julia T. Wycherley; Inga Zeisset (Biodiversity and Conservation, 2005)

Optimal mechanisms for finding and selecting mates: how threespine stickleback ( Gasterosteus aculeatus ) should encode male throat colors - M. P. Rowe; C. L. Baube; E. R. Loew; J. B. Phillips (Journal of Comparative Physiology A, 2004)

Seasonal profiles in growth, energy reserves, gonad development, and plasma steroids in age 1+ cultured Chinook salmon (Oncorhynchus tshawytscha) females - M. J. Unwin; C. W. Poortenaar; D. K. Rowe; N. C. Boustead; M. J. R. Porter (New Zealand Journal of Marine and Freshwater Research, 2004)
Sexual maturation in 2‐year‐old female Chinook salmon (Oncorhynchus tshawytscha) is unknown within their native range, but occurs in up to 20% of farmed stocks in New Zealand. To characterise the seasonal timing of oogenesis and subsequent ovarian development, we measured levels of plasma 17β‐estradiol and testosterone, condition factor, and gonadosomatic and hepatosomatic index, for freshwater‐reared female Chinook at 2–4‐week intervals during their second year of life (May 2001‐April 2002). These comprised two treatment groups under additional 24 h illumination from September to January, and two ambient controls. Macroscopic ovarian development first occurred in mid September (8 months before spawning), coinciding with detectable increases (≥0.3 ng ml ‐1 ) in both plasma steroids. Vitellogenesis was first observed in November and coincided with an increase in hepatosomatic index, possibly indicating the liver's role in transferring lipids to the developing ova. Neither mean weight nor the percentage of maturating fish (mean 6.9%) differed between the treatment and control groups at the end of the experiment, but ovarian development in the treatment group was advanced by 13 days relative to the controls. Reduced dark phase plasma melatonin levels confirmed that the additional light was sufficiently intense to produce a physiological response in the artificially illuminated fish.

Conserved simple sequence repeats for the Limnanthaceae (Brassicales) - V. K. Kishore; P. Velasco; D. K. Shintani; J. Rowe; C. Rosato; N. Adair; M. B. Slabaugh; S. J. Knapp (Theoretical and Applied Genetics, 2004)

Chemical Contaminants and their Effects in Fish and Wildlife from the Industrial Zone of Sumgayit, Republic of Azerbaijan - Carol D. Swartz; K.C. Donnelly; Arif Islamzadeh; Gilbert T. Rowe; William J. Rogers; Grigoriy M. Palatnikov; Arif A. Mekhtiev; Rafik Kasimov; Thomas J. McDonald; Jeffery K. Wickliffe; Bobby J. Presley; John W. Bickham (Ecotoxicology, 2003)

Editorial: The Unknown Environmental Tragedy in Sumgayit, Azerbaijan - John W. Bickham; Cole W. Matson; Arif Islamzadeh; Gilbert T. Rowe; K.C. Donnelly; Carol D. Swartz; William J. Rogers; Jeffrey K. Wickliffe; Robin L. Autenrieth; Thomas J. McDonald; Dmitri Politov; Grigoriy Palatnikov; et al. (Ecotoxicology, 2003)

Spawning behaviour and acoustic communication in Atlantic cod - S. Rowe; J. A. Hutchings (Journal of Fish Biology, 2003)
Mating systems are defined by the pattern of matings among individuals in a population, including the number of mates obtained by each female and male, and the duration of pair bonds. Within all mating systems, mate choice, intra‐sexual competition, and sperm competition may lead to variation in mating success among individuals. Growing evidence indicates that quantification of the patterns and processes of mating may be critical to understanding population dynamics. Atlantic cod had been fished for hundreds of years and was one of the most important commercial fish species worldwide until the recent collapse of many populations. Despite being of theoretical interest and practical importance, little was known about this species’ reproductive behaviour. Our research employed a quantitative approach to understand causes and consequences of variation in the mating system of Atlantic cod at the individual and population levels. We incorporated both detailed behavioural studies in the laboratory and observations of cod captured in the commercial fishery. Preliminary observations indicate tremendous variation in reproductive behaviour and mating success both within and between populations. Furthermore, variation in reproductive behaviour and mating success appears to be related to the ability of males to produce sound. Knowledge of Atlantic cod spawning behaviour will likely contribute to better understanding of population dynamics and improved ability to predict the impact of fishing on cod populations.

Predicting Biogeochemical Calcium Precipitation in Landfill Leachate Collection Systems - Jamie F. VanGulck; R. Kerry Rowe; Bruce E. Rittmann; Andrew J. Cooke (Biodegradation, 2003)

Probing conformation and conformational change in proteins is optimally undertaken in relative mode - Neil Errington; Arthur J. Rowe (European Biophysics Journal, 2003)

Phylogenetic relationships of dengue-1 viruses from Argentina and Paraguay - G. Avilés; J. Rowe; J. Meissner; J. C. Manzur Caffarena; D. Enria; S. St. Jeor (Archives of Virology, 2002)

Isolation and characterization of microsatellite primers for the Fragrant Orchid Gymnadenia conopsea (L.) R. Brown (Orchidaceae) - Victoria V. Campbell; Graham Rowe; Trevor J.C. Beebee; Michael J. Hutchings (Conservation Genetics, 2002)

Accumulation and Selective Maternal Transfer of Contaminants in the Turtle Trachemys scripta Associated with Coal Ash Deposition - R. D. Nagle, C. L. Rowe, J. D. Congdon (Archives of Environmental Contamination and Toxicology, 2001)

Considerations on the use of video playbacks as visual stimuli: the Lisbon workshop consensus - R. F. Oliveira; G. G. Rosenthal; I. Schlupp; P. K. McGregor; I. C. Cuthill; J. A. Endler; L. J. Fleishman; J. Zeil; E. Barata; F. Burford; D. Gonçalves; M. Haley; et al. (acta ethologica, 2000)

Polymerase chain reaction primers for microsatellite loci in the north European water frogs Rana ridibunda and R. lessonae - Inga Zeisset; Graham Rowe; Trevor J. C. Beebee (Molecular Ecology, 2000)

Isotopic composition of xenon in petroleum from the shell bullwinkle field - J. Nuzzo; M. Hyman; M. W. Rowe; M. N. Rao; R. L. Palma; J. Westrich (Journal of Earth System Science, 2000)

U-series dating of Hoxnian interglacial deposits at Marks Tey, Essex, England - P. J. Rowe; T. C. Atkinson; C. Turner (Journal of Quaternary Science, 1999)

U‐series dating of Hoxnian interglacial deposits at Marks Tey, Essex, England - P. J. Rowe; T. C. Atkinson; C. Turner (Journal of Quaternary Science, 1999)

Relationship between bisphosphonate concentration and osteoclast activity and viability - Dorothy J. Rowe; Lois A. Etre; Michael J. Lovdahl; Donald J. Pietrzyk (In Vitro Cellular & Developmental Biology - Animal, 1999)

Acute and Genotoxic Effects of Baku Harbor Sediment on Russian Sturgeon, Acipenser guildensteidti - J. W. Bickham; G. T. Rowe; G. Palatnikov; A. Mekhtiev; M. Mekhtiev; R. Y. Kasimov; D. W. Hauschultz; J. K. Wickliffe; W. J. Rogers (Bulletin of Environmental Contamination and Toxicology, 1998)

Elevated Trace Element Concentrations in Southern Toads, Bufo terrestris, Exposed to Coal Combustion Waste - W. A. Hopkins; M. T. Mendonça; C. L. Rowe; J. D. Congdon (Archives of Environmental Contamination and Toxicology, 1998)

Archive Contributions to a Molecular Phylogeography of the Toad Bufo calamita in Britain - T. J. C. Beebee; G. Rowe; T. Burke (Biochemical Genetics, 1998)

Phylogeography of the natterjack toad Bufo calamita in Britain: genetic differentiation of native and translocated populations - G. ROWE; T. J. C. BEEBEE; T. BURKE (Molecular Ecology, 1998)
The natterjack toad Bufo calamita is rare in Britain, which is at the northwestern edge of its biogeographical range. We investigated the level of genetic differentiation amongst almost all (34 out of 38) of the surviving British populations of this species, and among six new populations established by translocations during the 1980s. For eight microsatellite loci, allele sizes and frequencies were analysed using samples from each of these populations. The populations clustered into three robustly differentiated groups, each of which corresponded with a geographical region (east/southeast England, Merseyside and Cumbria). The Cumbrian populations showed a further weak geographical substructuring into northern and southern clades. The populations in south Cumbria were genetically more diverse than those in any of the other regions, as judged by the mean numbers of alleles per locus and the mean heterozygosity estimates. The translocated populations clustered close to their founders and, with one exception, did not differ significantly with respect to mean allele numbers, heterozygosity or polymorphism level. However, significant genetic differentiation (as measured by unbiased R ST ) was found between all but one of the founder‐translocation pairs. The implications of this phylogeographic study for the future conservation of B. calamita in Britain are discussed.

Radiometric dating of the Middle Palaeolithic tool industry and associated fauna of Pin Hole Cave, Creswell Crags, England - Roger M. Jacobi; Peter J. Rowe; Mabs A. Gilmour; Rainer Grün; Timothy C. Atkinson (Journal of Quaternary Science, 1998)

Radiometric dating of the Middle Palaeolithic tool industry and associated fauna of Pin Hole Cave, Creswell Crags, England - Roger M. Jacobi; Peter J. Rowe; Mabs A. Gilmour; Rainer Grün; Timothy C. Atkinson (Journal of Quaternary Science, 1998)

Physical characterization and ATPase activity of 14S dynein fractions from Tetrahymena thermophila - Hazel A. Tharia; Arthur J. Rowe; Olwyn Byron; Christine Wells (Journal of Muscle Research and Cell Motility, 1997)

Snr , New Genetic Loci Common to the Nitrate Reduction Systems of Pseudomonas aeruginosa PAO1 - Vida R. Irani; Al. Darzins; John J. Rowe (Current Microbiology, 1997)

Characterisation of the low affinity interaction between rat cell adhesion molecules CD2 and CD48 by analytical ultracentrifugation - H. Silkowski; S. J. Davis; A. Neil Barclay; Arthur J. Rowe; Stephen E. Harding; Olwyn Byron (European Biophysics Journal, 1997)

Further analysis of the role of spectrin repeat motifs in α-actinin dimer formation - G. Flood; A. J. Rowe; D. R. Critchley; W. B. Gratzer (European Biophysics Journal, 1997)

Analysis of data captured by an on-line image capture system from an analytical ultracentrifuge using schlieren optics - A. C. Clewlow; N. Errington; A. J. Rowe (European Biophysics Journal, 1997)

Migration between nests in the Australian arid‐zone ant Rhytidoponera sp. 12 revealed by DGGE analyses of mitochondrial DNA - W. Tek Tay; J. M. Cook; D. J. Rowe; R. H. Crozier (Molecular Ecology, 1997)
Denaturing gradient gel electrophoresis (DGGE) of a PCR‐amplified region of the mitochondrial DNA (mtDNA) including a large part of the cytochrome b gene revealed four haplotypes among worker ants from 75 colonies of the queenless ant Rhytidoponera sp. 12. The DGGE results were checked by sequencing examples of the haplotypes; all changes were transitions and two haplotypes differed by only a single substitution. Previous work (e.g. Crozier et al. 1984) showed that intranest relatedness is low for nuclear genes yet neighbouring nests are related; gene flow via winged males appeared the best explanation for this phenomenon. Two mtDNA haplotypes were found in 34.7% of the colonies studied, showing that female movement also occurs between nests. Migration of mated individuals on such a large scale when the number of reproductives is relatively small is unexpected (Crozier & Pamilo 1996). An observed tendency to clumping of the haplotypes is in accordance with the wingless nature of the female dispersers.

PCR primers for polymorphic microsatellite loci in the anuran amphibian Bufo calamita - G. Rowe; T. J. C. Beebee; T. Burke (Molecular Ecology, 1997)

An intact peripheral nerve preparation for monitoring inputs from single muscle afferent fibres - P. D. Mackie; M. J. Rowe (Experimental Brain Research, 1997)

Chromatographic studies on the origin of the cultivated diploid potatosolanum × ajanhuiri juz. et buk - Z. Huamán; J. G. Hawkes; P. R. Rowe (American Journal of Potato Research, 1983)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

The accumulation and loss of dieldrin and endrin in the Eastern oyster - J. W. Mason; D. R. Rowe (Archives of Environmental Contamination and Toxicology, 1976)

s 60th annual PAA meeting (Part II) - J. Landeo; P. R. Rowe; M. Mayer de Scurrah; M. T. Jackson; P. R. Rowe; J. G. Hawkes; P. Jatala; H. A. Mendoza; F. L. Haynes; G. C. C. Tai; H. Dejong; N. S. Wright; et al. (American Journal of Potato Research, 1976)

s 60th annual meeting The Potato Association of America - R. Kunkel; N. M. Holstad; R. E. Thornton; J. C. Bishop; Herman Timm; V. C. Shekhar; W. M. Iritani; Thornton Robert; Gary Hyde; Malamud Oscar; Robert B. O’Keefe; Mccown Brent; et al. (American Journal of Potato Research, 1976)

s 59th annual meeting Potato Association of America - D. E. Hudson; M. D. Volz; B. B. DePhillips; Gene A. Mathia; Frank Haynes; N. A. Wynn; Allen E. Abrahams; Lewis A. Schaper; Paul H. Orr; Earl C. Yaeger; Combs Joseph; Robert L. Mercer; et al. (American Journal of Potato Research, 1975)

Editorial - E. Norrby; W. P. Rowe; C. Scholtissek; D. A. J. Tyrrell; J. Vilček (Archives of Virology, 1975)

K. F. Meyer - S. Gard; C. Hallauer; A. Mayr; W. P. Rowe; J. Vilček (Archives of Virology, 1974)

Rat coronavirus (RCV): A prevalent, naturally occurring pneumotropic virus of rats - J. C. Parker; S. S. Cross; W. P. Rowe (Archives of Virology, 1970)